Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

De novo TRIM8 variants impair its protein localization to nuclear bodies and cause developmental delay, epilepsy, and focal segmental glomerulosclerosis. - Weng, Patricia L; Majmundar, Amar J; Khan, Kamal; Lim, Tze Y; Shril, Shirlee; Jin, Gina; Musgrove, John; Wang, Minxian; Ahram, Dina F; Aggarwal, Vimla S; Bier, Louise E; Heinzen, Erin L; et al. (Am J Hum Genet, 2021)
Focal segmental glomerulosclerosis (FSGS) is the main pathology underlying steroid-resistant nephrotic syndrome (SRNS) and a leading cause of chronic kidney disease. Monogenic forms of pediatric SRNS are predominantly caused by recessive mutations, while the contribution of de novo variants (DNVs) to this trait is poorly understood. Using exome sequencing (ES) in a proband with FSGS/SRNS, developmental delay, and epilepsy, we discovered a nonsense DNV in TRIM8, which encodes the E3 ubiquitin ligase tripartite motif containing 8. To establish whether TRIM8 variants represent a cause of FSGS, we aggregated exome/genome-sequencing data for 2,501 pediatric FSGS/SRNS-affected individuals and 48,556 control subjects, detecting eight heterozygous TRIM8 truncating variants in affected subjects but none in control subjects (p = 3.28 × 10). In all six cases with available parental DNA, we demonstrated de novo inheritance (p = 2.21 × 10). Reverse phenotyping revealed neurodevelopmental disease in all eight families. We next analyzed ES from 9,067 individuals with epilepsy, yielding three additional families with truncating TRIM8 variants. Clinical review revealed FSGS in all. All TRIM8 variants cause protein truncation clustering within the last exon between residues 390 and 487 of the 551 amino acid protein, indicating a correlation between this syndrome and loss of the TRIM8 C-terminal region. Wild-type TRIM8 overexpressed in immortalized human podocytes and neuronal cells localized to nuclear bodies, while constructs harboring patient-specific variants mislocalized diffusely to the nucleoplasm. Co-localization studies demonstrated that Gemini and Cajal bodies frequently abut a TRIM8 nuclear body. Truncating TRIM8 DNVs cause a neuro-renal syndrome via aberrant TRIM8 localization, implicating nuclear bodies in FSGS and developmental brain disease.
Keywords: Adult; Animals; Carrier Proteins; Cell Line; Child; Child, Preschool; Codon, Nonsense; Developmental Disabilities; Epilepsy; Female; Glomerulosclerosis, Focal Segmental; Humans; Intranuclear Space; Kidney; Male; Mice; Mutation; Nephrotic Syndrome; Nerve Tissue Proteins; Phenotype; Podocytes; Whole Exome Sequencing

Identification of homozygous mutations for hearing loss. - Dianatpour, Mehdi; Smith, Emily; Hashemi, Seyed Basir; Farazifard, Mohammad A; Nezafat, Navid; Razban, Vahid; Mani, Arya (Gene, 2021)
BACKGROUND: Hearing loss is the most common sensory disorder worldwide, affecting about 1 out of every 1000 newborns. The disease has major genetic components, and can be inherited as a single gene disorder either in autosomal dominant or recessive fashions. Due to the high rate of consanguineous unions, Iran has one of the highest prevalence of autosomal recessive nonsyndromic deafness (ARNSD) in the world. METHODS: We carried out a genetic screening of ten Iranian kindreds with more than one offspring affected by ARNSD caused by consanguineous unions. Sanger sequencing and whole exome sequencing together with in silico 3D structure modeling and protein stability prediction were used to identify the underlying disease causing genes. CONCLUSION: We identified the causes of deafness in all 10 kindred. In six kindreds homozygous mutations were identified in GJB2 gene by Sanger sequencing. By using whole exome sequencing (WES), a homozygous missense mutation was identified in ESRRB gene as the first ever reported disease gene in Iran. Also two novel homozygous frameshift and missense mutations were identified in MYO15A gene and one previously reported mutation in TMC1 gene in three independent kindred. Our study shows the efficacy of WES for unraveling new pathogenic mutations in ARNSD patients and expands the spectrum of genes contributing to ARNSD in the Iranian population. The findings of our study can facilitate future genetic screening of patients with ARNSD , early screening and optimal design of novel therapeutics.
Keywords: Connexin 26; Consanguinity; Female; Frameshift Mutation; Genetic Predisposition to Disease; Hearing Loss; Homozygote; Humans; Iran; Male; Membrane Proteins; Models, Molecular; Mutation, Missense; Myosins; Pedigree; Protein Stability; Receptors, Estrogen; Whole Exome Sequencing

MED27 Variants Cause Developmental Delay, Dystonia, and Cerebellar Hypoplasia. - Meng, Linyan; Isohanni, Pirjo; Shao, Yunru; GrAHm, Brett H; Hickey, Scott E; Brooks, Stephanie; Suomalainen, Anu; Joset, Pascal; Steindl, Katharina; Rauch, Anita; Hackenberg, Annette; High, Frances A; et al. (Ann Neurol, 2021)
The Mediator multiprotein complex functions as a regulator of RNA polymerase II-catalyzed gene transcription. In this study, exome sequencing detected biallelic putative disease-causing variants in MED27, encoding Mediator complex subunit 27, in 16 patients from 11 families with a novel neurodevelopmental syndrome. Patient phenotypes are highly homogeneous, including global developmental delay, intellectual disability, axial hypotonia with distal spasticity, dystonic movements, and cerebellar hypoplasia. Seizures and cataracts were noted in severely affected individuals. Identification of multiple patients with biallelic MED27 variants supports the critical role of MED27 in normal human neural development, particularly for the cerebellum. ANN NEUROL 2021;89:828-833.
Keywords: Adolescent; Adult; Amino Acid Sequence; Cataract; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Dystonia; Epilepsy; Genetic Variation; Humans; Infant; Mediator Complex; Nervous System Malformations; Phenotype; Whole Exome Sequencing

Mutations in transcription factor CP2-like 1 may cause a novel syndrome with distal renal tubulopathy in humans. - Klämbt, Verena; Werth, Max; Onuchic-Whitford, Ana C; Getwan, Maike; Kitzler, Thomas M; Buerger, Florian; Mao, Youying; Deutsch, Konstantin; Mann, Nina; Majmundar, Amar J; Kaminski, Michael M; Shen, Tian; et al. (Nephrol Dial Transplant, 2021)
BACKGROUND: An underlying monogenic cause of early-onset chronic kidney disease (CKD) can be detected in ∼20% of individuals. For many etiologies of CKD manifesting before 25 years of age, >200 monogenic causative genes have been identified to date, leading to the elucidation of mechanisms of renal pathogenesis. METHODS: In 51 families with echogenic kidneys and CKD, we performed whole-exome sequencing to identify novel monogenic causes of CKD. RESULTS: We discovered a homozygous truncating mutation in the transcription factor gene transcription factor CP2-like 1 (TFCP2L1) in an Arabic patient of consanguineous descent. The patient developed CKD by the age of 2 months and had episodes of severe hypochloremic, hyponatremic and hypokalemic alkalosis, seizures, developmental delay and hypotonia together with cataracts. We found that TFCP2L1 was localized throughout kidney development particularly in the distal nephron. Interestingly, TFCP2L1 induced the growth and development of renal tubules from rat mesenchymal cells. Conversely, the deletion of TFCP2L1 in mice was previously shown to lead to reduced expression of renal cell markers including ion transporters and cell identity proteins expressed in different segments of the distal nephron. TFCP2L1 localized to the nucleus in HEK293T cells only upon coexpression with its paralog upstream-binding protein 1 (UBP1). A TFCP2L1 mutant complementary DNA (cDNA) clone that represented the patient's mutation failed to form homo- and heterodimers with UBP1, an essential step for its transcriptional activity. CONCLUSION: Here, we identified a loss-of-function TFCP2L1 mutation as a potential novel cause of CKD in childhood accompanied by a salt-losing tubulopathy.
Keywords: Animals; Child; DNA-Binding Proteins; Epithelial-Mesenchymal Transition; Female; HEK293 Cells; Humans; Kidney Diseases; Mice; Mice, Knockout; Mutation; Rats; Repressor Proteins; Single-Cell Analysis; Transcription Factors; Whole Exome Sequencing

Variants in GNAI1 cause a syndrome associated with variable features including developmental delay, seizures, and hypotonia. - Muir, Alison M; Gardner, Jennifer F; van Jaarsveld, Richard H; de Lange, Iris M; van der Smagt, Jasper J; Wilson, Golder N; Dubbs, Holly; Goldberg, Ethan M; Zitano, Lia; Bupp, Caleb; Martinez, Jose; Srour, Myriam; et al. (Genet Med, 2021)
PURPOSE: Neurodevelopmental disorders (NDDs) encompass a spectrum of genetically heterogeneous disorders with features that commonly include developmental delay, intellectual disability, and autism spectrum disorders. We sought to delineate the molecular and phenotypic spectrum of a novel neurodevelopmental disorder caused by variants in the GNAI1 gene. METHODS: Through large cohort trio-based exome sequencing and international data-sharing, we identified 24 unrelated individuals with NDD phenotypes and a variant in GNAI1, which encodes the inhibitory Gαi1 subunit of heterotrimeric G-proteins. We collected detailed genotype and phenotype information for each affected individual. RESULTS: We identified 16 unique variants in GNAI1 in 24 affected individuals; 23 occurred de novo and 1 was inherited from a mosaic parent. Most affected individuals have a severe neurodevelopmental disorder. Core features include global developmental delay, intellectual disability, hypotonia, and epilepsy. CONCLUSION: This collaboration establishes GNAI1 variants as a cause of NDDs. GNAI1-related NDD is most often characterized by severe to profound delays, hypotonia, epilepsy that ranges from self-limiting to intractable, behavior problems, and variable mild dysmorphic features.
Keywords: Child; Developmental Disabilities; Humans; Intellectual Disability; Muscle Hypotonia; Neurodevelopmental Disorders; Seizures; Whole Exome Sequencing

Association of Rare Pathogenic DNA Variants for Familial Hypercholesterolemia, Hereditary Breast and Ovarian Cancer Syndrome, and Lynch Syndrome With Disease Risk in Adults According to Family History. - Patel, Aniruddh P; Wang, Minxian; Fahed, Akl C; Mason-Suares, Heather; Brockman, Deanna; Pelletier, Renee; Amr, Sami; Machini, Kalotina; Hawley, Megan; Witkowski, Leora; Koch, Christopher; Philippakis, Anthony; et al. (JAMA Netw Open, 2020)
Importance: Pathogenic DNA variants associated with familial hypercholesterolemia, hereditary breast and ovarian cancer syndrome, and Lynch syndrome are widely recognized as clinically important and actionable when identified, leading some clinicians to recommend population-wide genomic screening. Objectives: To assess the prevalence and clinical importance of pathogenic or likely pathogenic variants associated with each of 3 genomic conditions (familial hypercholesterolemia, hereditary breast and ovarian cancer syndrome, and Lynch syndrome) within the context of contemporary clinical care. Design, Setting, and Participants: This cohort study used gene-sequencing data from 49 738 participants in the UK Biobank who were recruited from 22 sites across the UK between March 21, 2006, and October 1, 2010. Inpatient hospital data date back to 1977; cancer registry data, to 1957; and death registry data, to 2006. Statistical analysis was performed from July 22, 2019, to November 15, 2019. Exposures: Pathogenic or likely pathogenic DNA variants classified by a clinical laboratory geneticist. Main Outcomes and Measures: Composite end point specific to each genomic condition based on atherosclerotic cardiovascular disease events for familial hypercholesterolemia, breast or ovarian cancer for hereditary breast and ovarian cancer syndrome, and colorectal or uterine cancer for Lynch syndrome. Results: Among 49 738 participants (mean [SD] age, 57 [8] years; 27 144 female [55%]), 441 (0.9%) harbored a pathogenic or likely pathogenic variant associated with any of 3 genomic conditions, including 131 (0.3%) for familial hypercholesterolemia, 235 (0.5%) for hereditary breast and ovarian cancer syndrome, and 76 (0.2%) for Lynch syndrome. Presence of these variants was associated with increased risk of disease: for familial hypercholesterolemia, 28 of 131 carriers (21.4%) vs 4663 of 49 607 noncarriers (9.4%) developed atherosclerotic cardiovascular disease; for hereditary breast and ovarian cancer syndrome, 32 of 116 female carriers (27.6%) vs 2080 of 27 028 female noncarriers (7.7%) developed associated cancers; and for Lynch syndrome, 17 of 76 carriers (22.4%) vs 929 of 49 662 noncarriers (1.9%) developed colorectal or uterine cancer. The predicted probability of disease at age 75 years despite contemporary clinical care was 45.3% for carriers of familial hypercholesterolemia, 41.1% for hereditary breast and ovarian cancer syndrome, and 38.3% for Lynch syndrome. Across the 3 conditions, 39.7% (175 of 441) of the carriers reported a family history of disease vs 23.2% (34 517 of 148 772) of noncarriers. Conclusions and Relevance: The findings suggest that approximately 1% of the middle-aged adult population in the UK Biobank harbored a pathogenic variant associated with any of 3 genomic conditions. These variants were associated with an increased risk of disease despite contemporary clinical care and were not reliably detected by family history.
Keywords: Aged; Cohort Studies; Colorectal Neoplasms, Hereditary Nonpolyposis; Female; Genetic Predisposition to Disease; Hereditary Breast and Ovarian Cancer Syndrome; Heterozygote; Humans; Hyperlipoproteinemia Type II; Male; Middle Aged; Pedigree; Proportional Hazards Models; United Kingdom; Whole Exome Sequencing

Biallelic GRM7 variants cause epilepsy, microcephaly, and cerebral atrophy. - Marafi, Dana; Mitani, Tadahiro; Isikay, Sedat; Hertecant, Jozef; Almannai, Mohammed; Manickam, Kandamurugu; Abou Jamra, Rami; El-Hattab, Ayman W; Rajah, Jaishen; Fatih, Jawid M; Du, Haowei; Karaca, Ender; et al. (Ann Clin Transl Neurol, 2020)
OBJECTIVE: Defects in ion channels and neurotransmitter receptors are implicated in developmental and epileptic encephalopathy (DEE). Metabotropic glutamate receptor 7 (mGluR7), encoded by GRM7, is a presynaptic G-protein-coupled glutamate receptor critical for synaptic transmission. We previously proposed GRM7 as a candidate disease gene in two families with neurodevelopmental disorders (NDDs). One additional family has been published since. Here, we describe three additional families with GRM7 biallelic variants and deeply characterize the associated clinical neurological and electrophysiological phenotype and molecular data in 11 affected individuals from six unrelated families. METHODS: Exome sequencing and family-based rare variant analyses on a cohort of 220 consanguineous families with NDDs revealed three families with GRM7 biallelic variants; three additional families were identified through literature search and collaboration with a clinical molecular laboratory. RESULTS: We compared the observed clinical features and variants of 11 affected individuals from the six unrelated families. Identified novel deleterious variants included two homozygous missense variants (c.2671G>A:p.Glu891Lys and c.1973G>A:p.Arg685Gln) and one homozygous stop-gain variant (c.1975C>T:p.Arg659Ter). Developmental delay, neonatal- or infantile-onset epilepsy, and microcephaly were universal. Three individuals had hypothalamic-pituitary-axis dysfunction without pituitary structural abnormality. Neuroimaging showed cerebral atrophy and hypomyelination in a majority of cases. Two siblings demonstrated progressive loss of myelination by 2 years in both and an acquired microcephaly pattern in one. Five individuals died in early or late childhood. CONCLUSION: Detailed clinical characterization of 11 individuals from six unrelated families demonstrates that rare biallelic GRM7 pathogenic variants can cause DEEs, microcephaly, hypomyelination, and cerebral atrophy.
Keywords: Adolescent; Alleles; Atrophy; Child; Child, Preschool; Cohort Studies; Consanguinity; Epilepsy; Female; Humans; Infant; Male; Microcephaly; Neurodevelopmental Disorders; Pedigree; Phenotype; Receptors, Metabotropic Glutamate; Whole Exome Sequencing

CNVs cause autosomal recessive genetic diseases with or without involvement of SNV/indels. - Yuan, Bo; Wang, Lei; Liu, Pengfei; Shaw, Chad; Dai, Hongzheng; Cooper, Lance; Zhu, Wenmiao; Anderson, Stephanie A; Meng, Linyan; Wang, Xia; Wang, Yue; Xia, Fan; et al. (Genet Med, 2020)
PURPOSE: Improved resolution of molecular diagnostic technologies enabled detection of smaller sized exonic level copy-number variants (CNVs). The contribution of CNVs to autosomal recessive (AR) conditions may be better recognized using a large clinical cohort. METHODS: We retrospectively investigated the CNVs' contribution to AR conditions in cases subjected to chromosomal microarray analysis (CMA, N = ~70,000) and/or clinical exome sequencing (ES, N = ~12,000) at Baylor Genetics; most had pediatric onset neurodevelopmental disorders. RESULTS: CNVs contributed to biallelic variations in 87 cases, including 81 singletons and three affected sibling pairs. Seventy cases had CNVs affecting both alleles, and 17 had a CNV and a single-nucleotide variant (SNV)/indel in trans. In total, 94.3% of AR-CNVs affected one gene; among these 41.4% were single-exon and 35.0% were multiexon partial-gene events. Sixty-nine percent of homozygous AR-CNVs were embedded in homozygous genomic intervals. Five cases had large deletions unmasking an SNV/indel on the intact allele for a recessive condition, resulting in multiple molecular diagnoses. CONCLUSIONS: AR-CNVs are often smaller in size, transmitted through generations, and underrecognized due to limitations in clinical CNV detection methods. Our findings from a large clinical cohort emphasized integrated CNV and SNV/indel analyses for precise clinical and molecular diagnosis especially in the context of genomic disorders.
Keywords: Child; DNA Copy Number Variations; Exons; Humans; INDEL Mutation; Retrospective Studies; Whole Exome Sequencing

Community-based recruitment and exome sequencing indicates high diagnostic yield in adults with intellectual disability. - Sabo, Aniko; Murdock, David; Dugan, Shannon; Meng, Qingchang; Gingras, Marie-Claude; Hu, Jianhong; Muzny, Donna; Gibbs, Richard (Mol Genet Genomic Med, 2020)
BACKGROUND: Establishing a genetic diagnosis for individuals with intellectual disability (ID) benefits patients and their families as it may inform the prognosis, lead to appropriate therapy, and facilitate access to medical and supportive services. Exome sequencing has been successfully applied in a diagnostic setting, but most clinical exome referrals are pediatric patients, with many adults with ID lacking a comprehensive genetic evaluation. METHODS: Our unique recruitment strategy involved partnering with service and education providers for individuals with ID. We performed exome sequencing and analysis, and clinical variant interpretation for each recruited family. RESULTS: All five families enrolled in the study opted-in for the return of genetic results. In three out of five families exome sequencing analysis identified pathogenic or likely pathogenic variants in KANSL1, TUSC3, and MED13L genes. Families discussed the results and any potential medical follow-up in an appointment with a board certified clinical geneticist. CONCLUSION: Our study suggests high yield of exome sequencing as a diagnostic tool in adult patients with ID who have not undergone comprehensive sequencing-based genetic testing. Research studies including an option of return of results through a genetic clinic could help minimize the disparity in exome diagnostic testing between pediatric and adult patients with ID.
Keywords: Adult; Female; Genetic Testing; Humans; Independent Living; Intellectual Disability; Male; Mediator Complex; Membrane Proteins; Nuclear Proteins; Patient Selection; Sensitivity and Specificity; Tumor Suppressor Proteins; Whole Exome Sequencing

Cytoplasmic "ciliary inclusions" in isolation are not sufficient for the diagnosis of primary ciliary dyskinesia. - Vece, Timothy J; Sagel, Scott D; Zariwala, Maimoona A; Sullivan, Kelli M; Burns, Kimberlie A; Dutcher, Susan K; Yusupov, Roman; Leigh, Margaret W; Knowles, Michael R (Pediatr Pulmonol, 2020)
BACKGROUND: The diagnosis of primary ciliary dyskinesia (PCD) is difficult and requires a combination of clinical features, nasal nitric oxide testing, cilia ultrastructural analysis by electron microscopy (EM), and genetics. A recently described cytoplasmic ultrastructural change termed "ciliary inclusions" was reported to be diagnostic of PCD; however, no supporting evidence of PCD was provided. In this study, we sought to confirm, or refute, the diagnosis of PCD in subjects with "ciliary inclusions" on EM. METHODS: Six subjects from five families with previous lab reports of "ciliary inclusions" on EMs of ciliated cells were identified and evaluated at a Genetic Disorders of Mucociliary Clearance Consortium site. We performed a detailed clinical history, nasal nitric oxide measurement, genetic testing including whole-exome sequencing (WES), and when possible, repeat ciliary EM study. RESULTS: Only one of six subjects had multiple and persistent clinical features congruent with PCD. No subject had situs inversus. Only one of six subjects had a very low nasal nitric oxide level. No "ciliary inclusions" were found in three subjects who had a repeat ciliary EM, and ciliary axonemal ultrastructures were normal. Genetic testing, including WES, was negative for PCD-causing genes, and for pathogenic variants in gene pathways that might cause "ciliary inclusions," such as ciliary biogenesis. CONCLUSION: "Ciliary Inclusions", in isolation, are not sufficient to diagnosis PCD. If seen, additional studies should be done to pursue an accurate diagnosis.
Keywords: Child, Preschool; Cilia; Ciliary Motility Disorders; Female; Genetic Testing; Humans; Infant; Male; Nasal Mucosa; Nitric Oxide; Whole Exome Sequencing

DAAM2 Variants Cause Nephrotic Syndrome via Actin Dysregulation. - Schneider, Ronen; Deutsch, Konstantin; Hoeprich, Gregory J; Marquez, Jonathan; Hermle, Tobias; Braun, Daniela A; Seltzsam, Steve; Kitzler, Thomas M; Mao, Youying; Buerger, Florian; Majmundar, Amar J; Onuchic-Whitford, Ana C; et al. (Am J Hum Genet, 2020)
The discovery of >60 monogenic causes of nephrotic syndrome (NS) has revealed a central role for the actin regulators RhoA/Rac1/Cdc42 and their effectors, including the formin INF2. By whole-exome sequencing (WES), we here discovered bi-allelic variants in the formin DAAM2 in four unrelated families with steroid-resistant NS. We show that DAAM2 localizes to the cytoplasm in podocytes and in kidney sections. Further, the variants impair DAAM2-dependent actin remodeling processes: wild-type DAAM2 cDNA, but not cDNA representing missense variants found in individuals with NS, rescued reduced podocyte migration rate (PMR) and restored reduced filopodia formation in shRNA-induced DAAM2-knockdown podocytes. Filopodia restoration was also induced by the formin-activating molecule IMM-01. DAAM2 also co-localizes and co-immunoprecipitates with INF2, which is intriguing since variants in both formins cause NS. Using in vitro bulk and TIRF microscopy assays, we find that DAAM2 variants alter actin assembly activities of the formin. In a Xenopus daam2-CRISPR knockout model, we demonstrate actin dysregulation in vivo and glomerular maldevelopment that is rescued by WT-DAAM2 mRNA. We conclude that DAAM2 variants are a likely cause of monogenic human SRNS due to actin dysregulation in podocytes. Further, we provide evidence that DAAM2-associated SRNS may be amenable to treatment using actin regulating compounds.
Keywords: Actins; Alleles; Animals; Animals, Genetically Modified; Cell Movement; Cytoplasm; Formins; Genetic Variation; Humans; Kidney; Kidney Glomerulus; Microfilament Proteins; Mutation, Missense; Nephrotic Syndrome; Podocytes; Pseudopodia; rho GTP-Binding Proteins; RNA, Small Interfering; Whole Exome Sequencing; Xenopus

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder. - Mirzaa, Ghayda M; Chong, Jessica X; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A; Sajan, Samin A; Tang, Sha; et al. (Genet Med, 2020)
PURPOSE: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). METHODS: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype-phenotype relationships. RESULTS: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. CONCLUSION: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Nerve Tissue Proteins; Neurodevelopmental Disorders; Neuroimaging; Whole Exome Sequencing

Exome sequencing implicates genetic disruption of prenatal neuro-gliogenesis in sporadic congenital hydrocephalus. - Jin, Sheng Chih; Dong, Weilai; Kundishora, Adam J; Panchagnula, Shreyas; Moreno-De-Luca, Andres; Furey, Charuta G; Allocco, August A; Walker, Rebecca L; Nelson-Williams, Carol; Smith, Hannah; Dunbar, Ashley; Conine, Sierra; et al. (Nat Med, 2020)
Congenital hydrocephalus (CH), characterized by enlarged brain ventricles, is considered a disease of excessive cerebrospinal fluid (CSF) accumulation and thereby treated with neurosurgical CSF diversion with high morbidity and failure rates. The poor neurodevelopmental outcomes and persistence of ventriculomegaly in some post-surgical patients highlight our limited knowledge of disease mechanisms. Through whole-exome sequencing of 381 patients (232 trios) with sporadic, neurosurgically treated CH, we found that damaging de novo mutations account for >17% of cases, with five different genes exhibiting a significant de novo mutation burden. In all, rare, damaging mutations with large effect contributed to ~22% of sporadic CH cases. Multiple CH genes are key regulators of neural stem cell biology and converge in human transcriptional networks and cell types pertinent for fetal neuro-gliogenesis. These data implicate genetic disruption of early brain development, not impaired CSF dynamics, as the primary pathomechanism of a significant number of patients with sporadic CH.
Keywords: Brain; Cerebral Ventricles; Exome; Female; Genetic Predisposition to Disease; Humans; Hydrocephalus; Male; Mutation; Neural Stem Cells; Neurogenesis; Neuroglia; Transcription Factors; Tripartite Motif Proteins; Ubiquitin-Protein Ligases; Whole Exome Sequencing

Expanding the phenotypic spectrum in RDH12-associated retinal disease. - Scott, Hilary A; Place, Emily M; Ferenchak, Kevin; Zampaglione, Erin; Wagner, Naomi E; Chao, Katherine R; DiTroia, Stephanie P; Navarro-Gomez, Daniel; Mukai, Shizuo; Huckfeldt, Rachel M; Pierce, Eric A; Bujakowska, Kinga M (Cold Spring Harb Mol Case Stud, 2020)
Retinol dehydrogenase 12, RDH12, plays a pivotal role in the visual cycle to ensure the maintenance of normal vision. Alterations in activity of this protein result in photoreceptor death and decreased vision beginning at an early age and progressing to substantial vision loss later in life. Here we describe 11 patients with retinal degeneration that underwent next-generation sequencing (NGS) with a targeted panel of all currently known inherited retinal degeneration (IRD) genes and whole-exome sequencing to identify the genetic causality of their retinal disease. These patients display a range of phenotypic severity prompting clinical diagnoses of macular dystrophy, cone-rod dystrophy, retinitis pigmentosa, and early-onset severe retinal dystrophy all attributed to biallelic recessive mutations in We report 15 causal alleles and expand the repertoire of known mutations with four novel variants: c.215A > G (p.Asp72Gly); c.362T > C (p.Ile121Thr); c.440A > C (p.Asn147Thr); and c.697G > A (p.Val233Ille). The broad phenotypic spectrum observed with biallelic mutations has been observed in other genetic forms of IRDs, but the diversity is particularly notable here given the prior association of primarily with severe early-onset disease. This breadth emphasizes the importance of broad genetic testing for inherited retinal disorders and extends the pool of individuals who may benefit from imminent gene-targeted therapies.
Keywords: Adolescent; Adult; Alcohol Oxidoreductases; Alleles; Amino Acid Substitution; Child; Child, Preschool; Female; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Humans; Male; Mutation; Optical Imaging; Pedigree; Phenotype; Retinal Diseases; Tomography, Optical Coherence; Whole Exome Sequencing; Young Adult

Genetic diagnoses in epilepsy: The impact of dynamic exome analysis in a pediatric cohort. - Rochtus, Anne; Olson, Heather E; Smith, Lacey; Keith, Louisa G; El Achkar, Christelle; Taylor, Alan; Mahida, Sonal; Park, Meredith; Kelly, McKenna; Shain, Catherine; Rockowitz, Shira; Rosen Sheidley, Beth; et al. (Epilepsia, 2020)
OBJECTIVE: We evaluated the yield of systematic analysis and/or reanalysis of whole exome sequencing (WES) data from a cohort of well-phenotyped pediatric patients with epilepsy and suspected but previously undetermined genetic etiology. METHODS: We identified and phenotyped 125 participants with pediatric epilepsy. Etiology was unexplained at the time of enrollment despite clinical testing, which included chromosomal microarray (57 patients), epilepsy gene panel (n = 48), both (n = 28), or WES (n = 8). Clinical epilepsy diagnoses included developmental and epileptic encephalopathy (DEE), febrile infection-related epilepsy syndrome, Rasmussen encephalitis, and other focal and generalized epilepsies. We analyzed WES data and compared the yield in participants with and without prior clinical genetic testing. RESULTS: Overall, we identified pathogenic or likely pathogenic variants in 40% (50/125) of our study participants. Nine patients with DEE had genetic variants in recently published genes that had not been recognized as epilepsy-related at the time of clinical testing (FGF12, GABBR1, GABBR2, ITPA, KAT6A, PTPN23, RHOBTB2, SATB2), and eight patients had genetic variants in candidate epilepsy genes (CAMTA1, FAT3, GABRA6, HUWE1, PTCHD1). Ninety participants had concomitant or subsequent clinical genetic testing, which was ultimately explanatory for 26% (23/90). Of the 67 participants whose molecular diagnoses were "unsolved" through clinical genetic testing, we identified pathogenic or likely pathogenic variants in 17 (25%). SIGNIFICANCE: Our data argue for early consideration of WES with iterative reanalysis for patients with epilepsy, particularly those with DEE or epilepsy with intellectual disability. Rigorous analysis of WES data of well-phenotyped patients with epilepsy leads to a broader understanding of gene-specific phenotypic spectra as well as candidate disease gene identification. We illustrate the dynamic nature of genetic diagnosis over time, with analysis and in some cases reanalysis of exome data leading to the identification of disease-associated variants among participants with previously nondiagnostic results from a variety of clinical testing strategies.
Keywords: Adolescent; Adult; Age of Onset; Brain Diseases; Child; Child, Preschool; Chromosomes, Human; Cohort Studies; Epilepsy; Epilepsy, Generalized; Exome; Female; Genetic Testing; Genetic Variation; Humans; Infant; Male; Microarray Analysis; Phenotype; Whole Exome Sequencing; Young Adult

Genome sequencing identifies a homozygous inversion disrupting QDPR as a cause for dihydropteridine reductase deficiency. - Lilleväli, Hardo; Pajusalu, Sander; Wojcik, Monica H; Goodrich, Julia; Collins, Ryan L; Murumets, Ülle; Tammur, Pille; Blau, Nenad; Lilleväli, Kersti; Õunap, Katrin (Mol Genet Genomic Med, 2020)
BACKGROUND: Dihydropteridine reductase (DHPR) is one of the key enzymes for maintaining in the organism the supply of tetrahydrobiopterin (BH ), an essential cofactor for aromatic amino acid hydroxylases. Its dysfunction causes the condition of hyperphenylalaninemia together with the lack of neurotransmitters. METHODS: We report a patient with biochemically diagnosed DHPR deficiency, with extensive molecular investigations undertaken to detect variations in quinoid dihydropteridine reductase (QDPR) gene. Sanger sequencing of QDPR coding regions, exome sequencing, QDPR mRNA PCR, and karyotyping were followed by trio genome sequencing. RESULTS: Short-read genome sequencing revealed a homozygous 9-Mb inversion disrupting QDPR. Structural variant breakpoints in chromosome 4 were located to intron 2 of QDPR at Chr4(GRCh38):g.17505522 and in intron 8 of the ACOX3 gene, Chr4(GRCh38):g.8398067). Both nonrelated parents carried the variant in heterozygous state. The inversion was not present in gnomAD structural variant database. CONCLUSION: Identification of the exact breakpoints now allows further straightforward molecular genetic testing of potential carriers of the inversion. This study extends the pathogenic variant spectrum of DHPR deficiency and highlights the role of structural variants in recessive metabolic disorders. To our knowledge, this is the first report on a large, canonical (rather than complex) homozygous pathogenic inversion detected by genome sequencing.
Keywords: Acyl-CoA Oxidase; Child; Chromosome Breakpoints; Chromosome Inversion; Chromosomes, Human, Pair 4; Female; Genetic Testing; Homozygote; Humans; Phenylketonurias; Whole Exome Sequencing

A genome-wide case-only test for the detection of digenic inheritance in human exomes. - Kerner, Gaspard; Bouaziz, Matthieu; Cobat, Aurelie; Bigio, Benedetta; Timberlake, Andrew T; Bustamante, Jacinta; Lifton, Richard P; Casanova, Jean-Laurent; Abel, Laurent (Proc Natl Acad Sci U S A, 2020)
Whole-exome sequencing (WES) has facilitated the discovery of genetic lesions underlying monogenic disorders. Incomplete penetrance and variable expressivity suggest a contribution of additional genetic lesions to clinical manifestations and outcome. Some monogenic disorders may therefore actually be digenic. However, only a few digenic disorders have been reported, all discovered by candidate gene approaches applied to at least one locus. We propose here a two-locus genome-wide test for detecting digenic inheritance in WES data. This approach uses the gene as the unit of analysis and tests all pairs of genes to detect pairwise gene × gene interactions underlying disease. It is a case-only method, which has several advantages over classic case-control tests, in particular by avoiding recruitment of controls. Our simulation studies based on real WES data identified two major sources of type I error inflation in this case-only test: linkage disequilibrium and population stratification. Both were corrected by specific procedures. Moreover, our case-only approach is more powerful than the corresponding case-control test for detecting digenic interactions in various population stratification scenarios. Finally, we confirmed the potential of our unbiased, genome-wide approach by successfully identifying a previously reported digenic lesion in patients with craniosynostosis. Our case-only test is a powerful and timely tool for detecting digenic inheritance in WES data from patients.
Keywords: Craniosynostoses; Epistasis, Genetic; Exome; Genetic Linkage; Genetic Variation; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Models, Genetic; Multifactorial Inheritance; Whole Exome Sequencing

Identification of genetic variants in CFAP221 as a cause of primary ciliary dyskinesia. - Bustamante-Marin, Ximena M; Shapiro, Adam; Sears, Patrick R; Charng, Wu-Lin; Conrad, Donald F; Leigh, Margaret W; Knowles, Michael R; Ostrowski, Lawrence E; Zariwala, Maimoona A (J Hum Genet, 2020)
Primary ciliary dyskinesia (PCD) is a rare disorder that affects the biogenesis or function of motile cilia resulting in chronic airway disease. PCD is genetically and phenotypically heterogeneous, with causative mutations identified in over 40 genes; however, the genetic basis of many cases is unknown. Using whole-exome sequencing, we identified three affected siblings with clinical symptoms of PCD but normal ciliary structure, carrying compound heterozygous loss-of-function variants in CFAP221. Computational analysis suggests that these variants are the most damaging alleles shared by all three siblings. Nasal epithelial cells from one of the subjects demonstrated slightly reduced beat frequency (16.5 Hz vs 17.7 Hz, p = 0.16); however, waveform analysis revealed that the CFAP221 defective cilia beat in an aberrant circular pattern. These results show that genetic variants in CFAP221 cause PCD and that CFAP221 should be considered a candidate gene in cases where PCD is suspected but cilia structure and beat frequency appear normal.
Keywords: Alleles; Calmodulin-Binding Proteins; Cilia; Ciliary Motility Disorders; Epithelial Cells; Exons; Genetic Variation; Humans; Mutation; Proteins; Whole Exome Sequencing

Inherited glomerular diseases in the gilded age of genomic advancements. - Gulati, Ashima; Dahl, Neera; Tufro, Alda (Pediatr Nephrol, 2020)
The synchronized advent of high-throughput next-generation sequencing technology and knowledge of the human genome has rendered exponential contributions to our understanding of the pathophysiology of glomerular kidney diseases. A genetic diagnosis can now be made or confirmed in about two-thirds of the suspected inherited glomerular diseases. Next-generation sequencing is adept at identifying single nucleotide variations and small insertions or deletions that constitute majority of the disease-causing mutations. Description of the complete mutation spectrum in syndromic glomerulopathies may require the use of both sequencing and cytogenetic methods to detect large structural DNA variation in addition to single nucleotide changes. The enthusiastic application of genetic and genomic knowledge to inherited glomerular diseases has uncovered anticipated and unforeseen challenges mainly related to the biological interpretation of variants of uncertain significance and the limited benefit on clinical management for the individual patient when a diagnosis is obtained. To attain the ultimate goal of transforming clinical decision-making based on accurate genetic diagnosis using genomic information, these challenges need to be addressed. Till then, the glory of genomic medicine stands the test of time in this gilded age of genomic advancements.
Keywords: Adolescent; Age Factors; Branchio-Oto-Renal Syndrome; Child; Female; High-Throughput Nucleotide Sequencing; Humans; Infant; Kidney Failure, Chronic; Male; Middle Aged; Mutation; Pedigree; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Whole Exome Sequencing

Large-Scale Exome Sequencing Study Implicates Both Developmental and Functional Changes in the Neurobiology of Autism. - Satterstrom, F Kyle; Kosmicki, Jack A; Wang, Jiebiao; Breen, Michael S; De Rubeis, Silvia; An, Joon-Yong; Peng, Minshi; Collins, Ryan; Grove, Jakob; Klei, Lambertus; Stevens, Christine; Reichert, Jennifer; et al. (Cell, 2020)
We present the largest exome sequencing study of autism spectrum disorder (ASD) to date (n = 35,584 total samples, 11,986 with ASD). Using an enhanced analytical framework to integrate de novo and case-control rare variation, we identify 102 risk genes at a false discovery rate of 0.1 or less. Of these genes, 49 show higher frequencies of disruptive de novo variants in individuals ascertained to have severe neurodevelopmental delay, whereas 53 show higher frequencies in individuals ascertained to have ASD; comparing ASD cases with mutations in these groups reveals phenotypic differences. Expressed early in brain development, most risk genes have roles in regulation of gene expression or neuronal communication (i.e., mutations effect neurodevelopmental and neurophysiological changes), and 13 fall within loci recurrently hit by copy number variants. In cells from the human cortex, expression of risk genes is enriched in excitatory and inhibitory neuronal lineages, consistent with multiple paths to an excitatory-inhibitory imbalance underlying ASD.
Keywords: Autistic Disorder; Case-Control Studies; Cell Lineage; Cerebral Cortex; Cohort Studies; Exome; Female; Gene Expression Regulation, Developmental; Gene Frequency; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Neurobiology; Neurons; Phenotype; Sex Factors; Single-Cell Analysis; Whole Exome Sequencing

Low-level parental somatic mosaic SNVs in exomes from a large cohort of trios with diverse suspected Mendelian conditions. - Gambin, Tomasz; Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Xie, Nina G; Wu, Lucia R; Yan, Yan Helen; Cao, Ye; Coban Akdemir, Zeynep H; Wilson, Theresa A; Jhangiani, Shalini N; Chen, Ed; et al. (Genet Med, 2020)
PURPOSE: The goal of this study was to assess the scale of low-level parental mosaicism in exome sequencing (ES) databases. METHODS: We analyzed approximately 2000 family trio ES data sets from the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) and Baylor Genetics (BG). Among apparent de novo single-nucleotide variants identified in the affected probands, we selected rare unique variants with variant allele fraction (VAF) between 30% and 70% in the probands and lower than 10% in one of the parents. RESULTS: Of 102 candidate mosaic variants validated using amplicon-based next-generation sequencing, droplet digital polymerase chain reaction, or blocker displacement amplification, 27 (26.4%) were confirmed to be low- (VAF between 1% and 10%) or very low (VAF <1%) level mosaic. Detection precision in parental samples with two or more alternate reads was 63.6% (BHCMG) and 43.6% (BG). In nine investigated individuals, we observed variability of mosaic ratios among blood, saliva, fibroblast, buccal, hair, and urine samples. CONCLUSION: Our computational pipeline enables robust discrimination between true and false positive candidate mosaic variants and efficient detection of low-level mosaicism in ES samples. We confirm that the presence of two or more alternate reads in the parental sample is a reliable predictor of low-level parental somatic mosaicism.
Keywords: Exome; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents; Whole Exome Sequencing

MN1 C-terminal truncation syndrome is a novel neurodevelopmental and craniofacial disorder with partial rhombencephalosynapsis. - Mak, Christopher C Y; Doherty, Dan; Lin, Angela E; Vegas, Nancy; Cho, Megan T; Viot, Géraldine; Dimartino, Clémantine; Weisfeld-Adams, James D; Lessel, Davor; Joss, Shelagh; Li, Chumei; Gonzaga-Jauregui, Claudia; et al. (Brain, 2020)
MN1 encodes a transcriptional co-regulator without homology to other proteins, previously implicated in acute myeloid leukaemia and development of the palate. Large deletions encompassing MN1 have been reported in individuals with variable neurodevelopmental anomalies and non-specific facial features. We identified a cluster of de novo truncating mutations in MN1 in a cohort of 23 individuals with strikingly similar dysmorphic facial features, especially midface hypoplasia, and intellectual disability with severe expressive language delay. Imaging revealed an atypical form of rhombencephalosynapsis, a distinctive brain malformation characterized by partial or complete loss of the cerebellar vermis with fusion of the cerebellar hemispheres, in 8/10 individuals. Rhombencephalosynapsis has no previously known definitive genetic or environmental causes. Other frequent features included perisylvian polymicrogyria, abnormal posterior clinoid processes and persistent trigeminal artery. MN1 is encoded by only two exons. All mutations, including the recurrent variant p.Arg1295* observed in 8/21 probands, fall in the terminal exon or the extreme 3' region of exon 1, and are therefore predicted to result in escape from nonsense-mediated mRNA decay. This was confirmed in fibroblasts from three individuals. We propose that the condition described here, MN1 C-terminal truncation (MCTT) syndrome, is not due to MN1 haploinsufficiency but rather is the result of dominantly acting C-terminally truncated MN1 protein. Our data show that MN1 plays a critical role in human craniofacial and brain development, and opens the door to understanding the biological mechanisms underlying rhombencephalosynapsis.
Keywords: Abnormalities, Multiple; Adolescent; Basilar Artery; Carotid Arteries; Cerebellar Vermis; Cerebellum; Child; Child, Preschool; Cohort Studies; Comparative Genomic Hybridization; Craniofacial Abnormalities; Female; Fibroblasts; Humans; Imaging, Three-Dimensional; Infant; Intellectual Disability; Language Development Disorders; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Nervous System Malformations; Nonsense Mediated mRNA Decay; Polymicrogyria; Real-Time Polymerase Chain Reaction; RNA-Seq; Syndrome; Tomography, X-Ray Computed; Trans-Activators; Tumor Suppressor Proteins; Whole Exome Sequencing; Whole Genome Sequencing

Monogenic variants in dystonia: an exome-wide sequencing study. - Zech, Michael; Jech, Robert; Boesch, Sylvia; Škorvánek, Matej; Weber, Sandrina; Wagner, Matias; Zhao, Chen; Jochim, Angela; Necpál, Ján; Dincer, Yasemin; Vill, Katharina; Distelmaier, Felix; et al. (Lancet Neurol, 2020)
BACKGROUND: Dystonia is a clinically and genetically heterogeneous condition that occurs in isolation (isolated dystonia), in combination with other movement disorders (combined dystonia), or in the context of multisymptomatic phenotypes (isolated or combined dystonia with other neurological involvement). However, our understanding of its aetiology is still incomplete. We aimed to elucidate the monogenic causes for the major clinical categories of dystonia. METHODS: For this exome-wide sequencing study, study participants were identified at 33 movement-disorder and neuropaediatric specialty centres in Austria, Czech Republic, France, Germany, Poland, Slovakia, and Switzerland. Each individual with dystonia was diagnosed in accordance with the dystonia consensus definition. Index cases were eligible for this study if they had no previous genetic diagnosis and no indication of an acquired cause of their illness. The second criterion was not applied to a subset of participants with a working clinical diagnosis of dystonic cerebral palsy. Genomic DNA was extracted from blood of participants and whole-exome sequenced. To find causative variants in known disorder-associated genes, all variants were filtered, and unreported variants were classified according to American College of Medical Genetics and Genomics guidelines. All considered variants were reviewed in expert round-table sessions to validate their clinical significance. Variants that survived filtering and interpretation procedures were defined as diagnostic variants. In the cases that went undiagnosed, candidate dystonia-causing genes were prioritised in a stepwise workflow. FINDINGS: We sequenced the exomes of 764 individuals with dystonia and 346 healthy parents who were recruited between June 1, 2015, and July 31, 2019. We identified causative or probable causative variants in 135 (19%) of 728 families, involving 78 distinct monogenic disorders. We observed a larger proportion of individuals with diagnostic variants in those with dystonia (either isolated or combined) with coexisting non-movement disorder-related neurological symptoms (100 [45%] of 222; excepting cases with evidence of perinatal brain injury) than in those with combined (19 [19%] of 98) or isolated (16 [4%] of 388) dystonia. Across all categories of dystonia, 104 (65%) of the 160 detected variants affected genes which are associated with neurodevelopmental disorders. We found diagnostic variants in 11 genes not previously linked to dystonia, and propose a predictive clinical score that could guide the implementation of exome sequencing in routine diagnostics. In cases without perinatal sentinel events, genomic alterations contributed substantively to the diagnosis of dystonic cerebral palsy. In 15 families, we delineated 12 candidate genes. These include IMPDH2, encoding a key purine biosynthetic enzyme, for which robust evidence existed for its involvement in a neurodevelopmental disorder with dystonia. We identified six variants in IMPDH2, collected from four independent cohorts, that were predicted to be deleterious de-novo variants and expected to result in deregulation of purine metabolism. INTERPRETATION: In this study, we have determined the role of monogenic variants across the range of dystonic disorders, providing guidance for the introduction of personalised care strategies and fostering follow-up pathophysiological explorations. FUNDING: Else Kröner-Fresenius-Stiftung, Technische Universität München, Helmholtz Zentrum München, Medizinische Universität Innsbruck, Charles University in Prague, Czech Ministry of Education, the Slovak Grant and Development Agency, the Slovak Research and Grant Agency.
Keywords: Adolescent; Child; Child, Preschool; Dystonia; Exome; Female; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Pedigree; Whole Exome Sequencing; Young Adult

The mutational constraint spectrum quantified from variation in 141,456 humans. - Karczewski, Konrad J; Francioli, Laurent C; Tiao, Grace; Cummings, Beryl B; Alföldi, Jessica; Wang, Qingbo; Collins, Ryan L; Laricchia, Kristen M; Ganna, Andrea; Birnbaum, Daniel P; Gauthier, Laura D; Brand, Harrison; et al. (Nature, 2020)
Genetic variants that inactivate protein-coding genes are a powerful source of information about the phenotypic consequences of gene disruption: genes that are crucial for the function of an organism will be depleted of such variants in natural populations, whereas non-essential genes will tolerate their accumulation. However, predicted loss-of-function variants are enriched for annotation errors, and tend to be found at extremely low frequencies, so their analysis requires careful variant annotation and very large sample sizes. Here we describe the aggregation of 125,748 exomes and 15,708 genomes from human sequencing studies into the Genome Aggregation Database (gnomAD). We identify 443,769 high-confidence predicted loss-of-function variants in this cohort after filtering for artefacts caused by sequencing and annotation errors. Using an improved model of human mutation rates, we classify human protein-coding genes along a spectrum that represents tolerance to inactivation, validate this classification using data from model organisms and engineered human cells, and show that it can be used to improve the power of gene discovery for both common and rare diseases.
Keywords: Adult; Brain; Cardiovascular Diseases; Cohort Studies; Databases, Genetic; Exome; Female; Genes, Essential; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Loss of Function Mutation; Male; Mutation Rate; Proprotein Convertase 9; Reproducibility of Results; RNA, Messenger; Whole Exome Sequencing; Whole Genome Sequencing

Mutations disrupting neuritogenesis genes confer risk for cerebral palsy. - Jin, Sheng Chih; Lewis, Sara A; Bakhtiari, Somayeh; Zeng, Xue; Sierant, Michael C; Shetty, Sheetal; Nordlie, Sandra M; Elie, Aureliane; Corbett, Mark A; Norton, Bethany Y; van Eyk, Clare L; Haider, Shozeb; et al. (Nat Genet, 2020)
In addition to commonly associated environmental factors, genomic factors may cause cerebral palsy. We performed whole-exome sequencing of 250 parent-offspring trios, and observed enrichment of damaging de novo mutations in cerebral palsy cases. Eight genes had multiple damaging de novo mutations; of these, two (TUBA1A and CTNNB1) met genome-wide significance. We identified two novel monogenic etiologies, FBXO31 and RHOB, and showed that the RHOB mutation enhances active-state Rho effector binding while the FBXO31 mutation diminishes cyclin D levels. Candidate cerebral palsy risk genes overlapped with neurodevelopmental disorder genes. Network analyses identified enrichment of Rho GTPase, extracellular matrix, focal adhesion and cytoskeleton pathways. Cerebral palsy risk genes in enriched pathways were shown to regulate neuromotor function in a Drosophila reverse genetics screen. We estimate that 14% of cases could be attributed to an excess of damaging de novo or recessive variants. These findings provide evidence for genetically mediated dysregulation of early neuronal connectivity in cerebral palsy.
Keywords: Animals; beta Catenin; Cerebral Palsy; Cyclin D; Cytoskeleton; Drosophila; Exome; Extracellular Matrix; F-Box Proteins; Female; Focal Adhesions; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Mutation; Neurites; rhoB GTP-Binding Protein; Risk Factors; Sequence Analysis, DNA; Signal Transduction; Tubulin; Tumor Suppressor Proteins; Whole Exome Sequencing

Mutations in ASPRV1 Cause Dominantly Inherited Ichthyosis. - Boyden, Lynn M; Zhou, Jing; Hu, Ronghua; Zaki, Theodore; Loring, Erin; Scott, Jared; Traupe, Heiko; Paller, Amy S; Lifton, Richard P; Choate, Keith A (Am J Hum Genet, 2020)
The discovery of genetic causes of inherited skin disorders has been pivotal to the understanding of epidermal differentiation, function, and renewal. Here we show via exome sequencing that mutations in ASPRV1 (aspartic peptidase retroviral-like 1) cause a dominant Mendelian disorder featuring palmoplantar keratoderma and lamellar ichthyosis, a phenotype that has otherwise been exclusively recessive. ASPRV1 encodes a mammalian-specific and stratified epithelia-specific protease important in processing of filaggrin, a critical component of the uppermost epidermal layer. Three different heterozygous ASPRV1 missense mutations in four unrelated ichthyosis kindreds segregate with disease and disrupt protein residues within close proximity to each other and autocatalytic cleavage sites. Expression of mutant ASPRV1 proteins demonstrates that all three mutations alter ASPRV1 auto-cleavage and filaggrin processing, a function vital to epidermal barrier integrity.
Keywords: Aspartic Acid Endopeptidases; Heredity; Heterozygote; Humans; Ichthyosis, Lamellar; Intermediate Filament Proteins; Mutation, Missense; Phenotype; Skin Diseases; Whole Exome Sequencing

Mutations in KRT10 in epidermolytic acanthoma. - Cheraghlou, Shayan; Atzmony, Lihi; Roy, Simon F; McNiff, Jennifer M; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Epidermolytic acanthoma (EA) is a rare acquired lesion demonstrating a characteristic histopathological pattern of epidermal degeneration referred to as epidermolytic hyperkeratosis (EHK). On histopathological analysis, EA appears nearly identical to inherited EHK-associated dermatoses such as epidermolytic ichthyosis and ichthyosis bullosa of Siemens. While it has been speculated that EA is caused by mutations in KRT10, KRT1, or KRT2 found in these inherited dermatoses, none have yet been identified. Herein, we aim to identify the contributions of keratin mutations to EA. METHODS: Using genomic DNA extracted from paraffin-embedded samples from departmental archives, we evaluated a discovery cohort using whole-exome sequencing (WES) and assessed remaining samples using Sanger sequencing screening and restriction fragment length polymorphism (RFLP) analysis. RESULTS: DNA from 16/20 cases in our sample was of sufficient quality for polymerase chain reaction amplification. WES of genomic DNA from lesional tissue revealed KRT10 c.466C > T, p.Arg156Cys mutations in 2/3 samples submitted for examination. RFLP analysis of these samples as well as eight additional samples confirmed the mutations identified via WES and identified four additional cases with Arg156 mutations. In sum, 6/11 screened cases showed hotspot mutation in KRT10. CONCLUSIONS: Hotspot mutations in the Arg156 position of KRT10, known to cause epidermolytic ichthyosis, also underlie EA.
Keywords: Acanthoma; Adult; Aged; Aged, 80 and over; Female; Genomics; Humans; Hyperkeratosis, Epidermolytic; Ichthyosis Bullosa of Siemens; Keratin-10; Keratins; Male; Middle Aged; Mutation; Skin Neoplasms; Whole Exome Sequencing

Mutations of the Transcriptional Corepressor ZMYM2 Cause Syndromic Urinary Tract Malformations. - Connaughton, Dervla M; Dai, Rufeng; Owen, Danielle J; Marquez, Jonathan; Mann, Nina; GrAHm-Paquin, Adda L; Nakayama, Makiko; Coyaud, Etienne; Laurent, Estelle M N; St-Germain, Jonathan R; Blok, Lot Snijders; Vino, Arianna; et al. (Am J Hum Genet, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) constitute one of the most frequent birth defects and represent the most common cause of chronic kidney disease in the first three decades of life. Despite the discovery of dozens of monogenic causes of CAKUT, most pathogenic pathways remain elusive. We performed whole-exome sequencing (WES) in 551 individuals with CAKUT and identified a heterozygous de novo stop-gain variant in ZMYM2 in two different families with CAKUT. Through collaboration, we identified in total 14 different heterozygous loss-of-function mutations in ZMYM2 in 15 unrelated families. Most mutations occurred de novo, indicating possible interference with reproductive function. Human disease features are replicated in X. tropicalis larvae with morpholino knockdowns, in which expression of truncated ZMYM2 proteins, based on individual mutations, failed to rescue renal and craniofacial defects. Moreover, heterozygous Zmym2-deficient mice recapitulated features of CAKUT with high penetrance. The ZMYM2 protein is a component of a transcriptional corepressor complex recently linked to the silencing of developmentally regulated endogenous retrovirus elements. Using protein-protein interaction assays, we show that ZMYM2 interacts with additional epigenetic silencing complexes, as well as confirming that it binds to FOXP1, a transcription factor that has also been linked to CAKUT. In summary, our findings establish that loss-of-function mutations of ZMYM2, and potentially that of other proteins in its interactome, as causes of human CAKUT, offering new routes for studying the pathogenesis of the disorder.
Keywords: Amphibian Proteins; Animals; Case-Control Studies; Child; Child, Preschool; DNA-Binding Proteins; Epigenesis, Genetic; Family; Female; Forkhead Transcription Factors; Heterozygote; Humans; Infant; Larva; Male; Mice; Mice, Knockout; Morpholinos; Mutation; Pedigree; Protein Binding; Repressor Proteins; Transcription Factors; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing; Xenopus

Paternal mosaicism for a novel PBX1 mutation associated with recurrent perinatal death: Phenotypic expansion of the PBX1-related syndrome. - Arts, Peer; Garland, Jessica; Byrne, Alicia B; Hardy, Tristan S E; Babic, Milena; Feng, Jinghua; Wang, Paul; Ha, Thuong; King-Smith, Sarah L; Schreiber, Andreas W; Crawford, April; Manton, Nick; et al. (Am J Med Genet A, 2020)
Autosomal dominant (de novo) mutations in PBX1 are known to cause congenital abnormalities of the kidney and urinary tract (CAKUT), with or without extra-renal abnormalities. Using trio exome sequencing, we identified a PBX1 p.(Arg107Trp) mutation in a deceased one-day-old neonate presenting with CAKUT, asplenia, and severe bilateral diaphragmatic thinning and eventration. Further investigation by droplet digital PCR revealed that the mutation had occurred post-zygotically in the father, with different variant allele frequencies of the mosaic PBX1 mutation in blood (10%) and sperm (20%). Interestingly, the father had subclinical hydronephrosis in childhood. With an expected recurrence risk of one in five, chorionic villus sampling and prenatal diagnosis for the PBX1 mutation identified recurrence in a subsequent pregnancy. The family opted to continue the pregnancy and the second affected sibling was stillborn at 35 weeks, presenting with similar severe bilateral diaphragmatic eventration, microsplenia, and complete sex reversal (46, XY female). This study highlights the importance of follow-up studies for presumed de novo and low-level mosaic variants and broadens the phenotypic spectrum of developmental abnormalities caused by PBX1 mutations.
Keywords: Congenital Abnormalities; Exome; Fathers; Female; Gene Frequency; Humans; Infant, Newborn; Kidney; Male; Mosaicism; Mutation; Perinatal Death; Pre-B-Cell Leukemia Transcription Factor 1; Pregnancy; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing

PEHO syndrome caused by compound heterozygote variants in ZNHIT3 gene. - Õunap, Katrin; Muru, Kai; Õiglane-Shlik, Eve; Ilves, Pilvi; Pajusalu, Sander; Kuus, Imbi; Wojcik, Monica H; Reimand, Tiia (Eur J Med Genet, 2020)
PEHO syndrome is characterized by Progressive Encephalopathy with Edema, Hypsarrhythmia, and Optic atrophy, which was first described in Finnish patients. A homozygous missense substitution p.Ser31Leu in ZNHIT3 was recently identified as the primary cause of PEHO syndrome in Finland. Variants in ZNHIT3 have not been identified in patients with PEHO or PEHO-like syndrome in other populations. It has therefore been suggested that PEHO syndrome caused by ZNHIT3 variants does not occur outside of the Finnish population. We describe the first patient outside Finland who carries compound heterozygous variants in ZNHIT3 gene causing PEHO syndrome. Trio genome sequencing was carried out and the identified variants were confirmed by Sanger sequencing. The patient filled all diagnostic clinical criteria of PEHO syndrome. We identified biallelic missense variants in ZNHIT3 gene: the c.92C > T p.(Ser31Leu) variant (NM_004773.3), which is described previously as causing PEHO syndrome and the second novel variant c.41G > T p.(Cys14Phe). There are only eight heterozygous carriers of c.41G > T variant in the gnomAD database and it is predicted damaging by multiple in silico algorithms. The ZNHIT3-associated PEHO syndrome exists outside of the Finnish population.
Keywords: Brain Edema; Databases, Genetic; Edema; Epileptic Syndromes; Female; Finland; Heterozygote; Humans; Infant, Newborn; Mutation, Missense; Neurodegenerative Diseases; Nuclear Proteins; Optic Atrophy; Phenotype; Spasms, Infantile; Transcription Factors; Whole Exome Sequencing; Whole Genome Sequencing

Phenotypic expansion of POGZ-related intellectual disability syndrome (White-Sutton syndrome). - Assia Batzir, Nurit; Posey, Jennifer E; Song, Xiaofei; Akdemir, Zeynep Coban; Rosenfeld, Jill A; Brown, Chester W; Chen, Emily; Holtrop, Shannon G; Mizerik, Elizabeth; Nieto Moreno, Margarita; Payne, Katelyn; Raas-Rothschild, Annick; et al. (Am J Med Genet A, 2020)
White-Sutton syndrome (WHSUS) is a recently-identified genetic disorder resulting from de novo heterozygous pathogenic variants in POGZ. Thus far, over 50 individuals have been reported worldwide, however phenotypic characterization and data regarding the natural history are still incomplete. Here we report the clinical features of 22 individuals with 21 unique loss of function POGZ variants. We observed a broad spectrum of intellectual disability and/or developmental delay with or without autism, and speech delay in all individuals. Other common problems included ocular abnormalities, hearing loss and gait abnormalities. A validated sleep disordered breathing questionnaire identified symptoms of obstructive sleep apnea in 4/12 (33%) individuals. A higher-than-expected proportion of cases also had gastrointestinal phenotypes, both functional and anatomical, as well as genitourinary anomalies. In line with previous publications, we observed an increased body mass index (BMI) z-score compared to the general population (mean 0.59, median 0.9; p 0.0253). Common facial features included microcephaly, broad forehead, midface hypoplasia, triangular mouth, broad nasal root and flat nasal bridge. Analysis of the Baylor Genetics clinical laboratory database revealed that POGZ variants were implicated in approximately 0.14% of cases who underwent clinical exome sequencing for neurological indications with or without involvement of other body systems. This study describes a greater allelic series and expands the phenotypic spectrum of this new syndromic form of intellectual disability and autism.
Keywords: Adolescent; Adult; Autistic Disorder; Child; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Microcephaly; Middle Aged; Mutation; Phenotype; Transposases; Whole Exome Sequencing; Young Adult

The pleiotropy associated with de novo variants in CHD4, CNOT3, and SETD5 extends to moyamoya angiopathy. - Pinard, Amelie; Guey, Stéphanie; Guo, Dongchuan; Cecchi, Alana C; Kharas, Natasha; Wallace, Stephanie; Regalado, Ellen S; Hostetler, Ellen M; Sharrief, Anjail Z; Bergametti, Françoise; Kossorotoff, Manoelle; Hervé, Dominique; et al. (Genet Med, 2020)
PURPOSE: Moyamoya angiopathy (MMA) is a cerebrovascular disease characterized by occlusion of large arteries, which leads to strokes starting in childhood. Twelve altered genes predispose to MMA but the majority of cases of European descent do not have an identified genetic trigger. METHODS: Exome sequencing from 39 trios were analyzed. RESULTS: We identified four de novo variants in three genes not previously associated with MMA: CHD4, CNOT3, and SETD5. Identification of additional rare variants in these genes in 158 unrelated MMA probands provided further support that rare pathogenic variants in CHD4 and CNOT3 predispose to MMA. Previous studies identified de novo variants in these genes in children with developmental disorders (DD), intellectual disability, and congenital heart disease. CONCLUSION: These genes encode proteins involved in chromatin remodeling, and taken together with previously reported genes leading to MMA-like cerebrovascular occlusive disease (YY1AP1, SMARCAL1), implicate disrupted chromatin remodeling as a molecular pathway predisposing to early onset, large artery occlusive cerebrovascular disease. Furthermore, these data expand the spectrum of phenotypic pleiotropy due to alterations of CHD4, CNOT3, and SETD5 beyond DD to later onset disease in the cerebrovascular arteries and emphasize the need to assess clinical complications into adulthood for genes associated with DD.
Keywords: Adult; Cell Cycle Proteins; Cerebrovascular Disorders; Child; Child, Preschool; Developmental Disabilities; DNA Helicases; Exome; Female; Genetic Predisposition to Disease; Humans; Intellectual Disability; Male; Methyltransferases; Mi-2 Nucleosome Remodeling and Deacetylase Complex; Middle Aged; Moyamoya Disease; Mutation; Nuclear Proteins; Transcription Factors; Whole Exome Sequencing

Recurrent homozygous damaging mutation in , encoding a protein disulfide isomerase, in four families with microlissencephaly. - Ghosh, Shereen Georges; Wang, Lu; Breuss, Martin W; Green, Joshua D; Stanley, Valentina; Yang, Xiaoxu; Ross, Danica; Traynor, Bryan J; Alhashem, Amal M; Azam, Matloob; Selim, Laila; Bastaki, Laila; et al. (J Med Genet, 2020)
BACKGROUND: Protein disulfide isomerase (PDI) proteins are part of the thioredoxin protein superfamily. PDIs are involved in the formation and rearrangement of disulfide bonds between cysteine residues during protein folding in the endoplasmic reticulum and are implicated in stress response pathways. METHODS: Eight children from four consanguineous families residing in distinct geographies within the Middle East and Central Asia were recruited for study. All probands showed structurally similar microcephaly with lissencephaly (microlissencephaly) brain malformations. DNA samples from each family underwent whole exome sequencing, assessment for repeat expansions and confirmatory segregation analysis. RESULTS: An identical homozygous variant in (c.500G>A), encoding thioredoxin-related transmembrane protein 2, segregated with disease in all four families. This variant changed the last coding base of exon 6, and impacted mRNA stability. All patients presented with microlissencephaly, global developmental delay, intellectual disability and epilepsy. While is an activator of cellular repeat expansion toxicity, patients showed no evidence of repeat expansions. CONCLUSION: The c.500G>A allele associates with recessive microlissencephaly, and patients show no evidence of expansions. is the first PDI implicated in a recessive disease, suggesting a protein isomerisation defect in microlissencephaly.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Consanguinity; Endoplasmic Reticulum; Exons; Female; Genetic Predisposition to Disease; Homozygote; Humans; Male; Membrane Proteins; Microcephaly; Mutation; Protein Disulfide-Isomerases; Protein Folding; Thioredoxins; Whole Exome Sequencing

Sequential targeted exome sequencing of 1001 patients affected by unexplained limb-girdle weakness. - Topf, Ana; Johnson, Katherine; Bates, Adam; Phillips, Lauren; Chao, Katherine R; England, Eleina M; Laricchia, Kristen M; Mullen, Thomas; Valkanas, Elise; Xu, Liwen; Bertoli, Marta; Blain, Alison; et al. (Genet Med, 2020)
PURPOSE: Several hundred genetic muscle diseases have been described, all of which are rare. Their clinical and genetic heterogeneity means that a genetic diagnosis is challenging. We established an international consortium, MYO-SEQ, to aid the work-ups of muscle disease patients and to better understand disease etiology. METHODS: Exome sequencing was applied to 1001 undiagnosed patients recruited from more than 40 neuromuscular disease referral centers; standardized phenotypic information was collected for each patient. Exomes were examined for variants in 429 genes associated with muscle conditions. RESULTS: We identified suspected pathogenic variants in 52% of patients across 87 genes. We detected 401 novel variants, 116 of which were recurrent. Variants in CAPN3, DYSF, ANO5, DMD, RYR1, TTN, COL6A2, and SGCA collectively accounted for over half of the solved cases; while variants in newer disease genes, such as BVES and POGLUT1, were also found. The remaining well-characterized unsolved patients (48%) need further investigation. CONCLUSION: Using our unique infrastructure, we developed a pathway to expedite muscle disease diagnoses. Our data suggest that exome sequencing should be used for pathogenic variant detection in patients with suspected genetic muscle diseases, focusing first on the most common disease genes described here, and subsequently in rarer and newly characterized disease genes.
Keywords: Anoctamins; Exome; Glucosyltransferases; Humans; Muscular Dystrophies, Limb-Girdle; Whole Exome Sequencing

Spectrum of genetic variants in moderate to severe sporadic hearing loss in Pakistan. - Ramzan, Memoona; Bashir, Rasheeda; Salman, Midhat; Mujtaba, Ghulam; Sobreira, Nara; Witmer, P Dane; Naz, Sadaf (Sci Rep, 2020)
Hearing loss affects 380 million people worldwide due to environmental or genetic causes. Determining the cause of deafness in individuals without previous family history of hearing loss is challenging and has been relatively unexplored in Pakistan. We investigated the spectrum of genetic variants in hearing loss in a cohort of singleton affected individuals born to consanguineous parents. Twenty-one individuals with moderate to severe hearing loss were recruited. We performed whole-exome sequencing on DNA samples from the participants, which identified seventeen variants in ten known deafness genes and one novel candidate gene. All identified variants were homozygous except for two. Eleven of the variants were novel, including one multi-exonic homozygous deletion in OTOA. A missense variant in ESRRB was implicated for recessively inherited moderate to severe hearing loss. Two individuals were heterozygous for variants in MYO7A and CHD7, respectively, consistent with de novo variants or dominant inheritance with incomplete penetrance as the reason for their hearing loss. Our results indicate that similar to familial cases of deafness, variants in a large number of genes are responsible for moderate to severe hearing loss in sporadic individuals born to consanguineous couples.
Keywords: Adolescent; Amino Acid Sequence; Audiometry, Pure-Tone; Child; Child, Preschool; Deafness; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Hearing Loss; Heterozygote; Homozygote; Humans; Mutation, Missense; Pakistan; Phenotype; Whole Exome Sequencing; Young Adult

Successful treatment of intractable epilepsy with ketogenic diet therapy in twins with ALG3-CDG. - Paketci, C; Edem, P; Hiz, S; Sonmezler, E; Soydemir, D; Sarikaya Uzan, G; Oktay, Y; O'Heir, E; Beltran, S; Laurie, S; Töpf, A; Lochmuller, H; et al. (Brain Dev, 2020)
BACKGROUND: Congenital disorders of glycosylation (CDG) is a heterogeneous group of congenital metabolic diseases with multisystem clinical involvement. ALG3-CDG is a very rare subtype with only 24 cases reported so far. CASE: Here, we report two siblings with dysmorphic features, growth retardation, microcephaly, intractable epilepsy, and hemangioma in the frontal, occipital and lumbosacral regions. RESULTS: We studied two siblings by whole exome sequencing. A pathogenic variant in ALG3 (NM_005787.6: c.165C > T; p.Gly55=) that had been previously associated with congenital glycolysis defect type 1d was identified. Their intractable seizures were controlled by ketogenic diet. CONCLUSION: Although prominent findings of growth retardation and microcephaly seen in our patients have been extensively reported before, presence of hemangioma is a novel finding that may be used as an indication for ALG3-CDG diagnosis. Our patients are the first reported cases whose intractable seizures were controlled with ketogenic diet. This report adds ketogenic diet as an option for treatment of intractable epilepsy in ALG3-CDG.
Keywords: Central Nervous System Neoplasms; Congenital Disorders of Glycosylation; Craniofacial Abnormalities; Developmental Disabilities; Diet, Ketogenic; Drug Resistant Epilepsy; Female; Hemangioma; Humans; Infant; Male; Mannosyltransferases; Twins; Whole Exome Sequencing

TBX6 missense variants expand the mutational spectrum in a non-Mendelian inheritance disease. - Chen, Weisheng; Lin, Jiachen; Wang, Lianlei; Li, Xiaoxin; Zhao, Sen; Liu, Jiaqi; Akdemir, Zeynep C; Zhao, Yanxue; Du, Renqian; Ye, Yongyu; Song, Xiaofei; Zhang, Yuanqiang; et al. (Hum Mutat, 2020)
Congenital scoliosis (CS) is a birth defect with variable clinical and anatomical manifestations due to spinal malformation. The genetic etiology underlying about 10% of CS cases in the Chinese population is compound inheritance by which the gene dosage is reduced below that of haploinsufficiency. In this genetic model, the trait manifests as a result of the combined effect of a rare variant and common pathogenic variant allele at a locus. From exome sequencing (ES) data of 523 patients in Asia and two patients in Texas, we identified six TBX6 gene-disruptive variants from 11 unrelated CS patients via ES and in vitro functional testing. The in trans mild hypomorphic allele was identified in 10 of the 11 subjects; as anticipated these 10 shared a similar spinal deformity of hemivertebrae. The remaining case has a homozygous variant in TBX6 (c.418C>T) and presents a more severe spinal deformity phenotype. We found decreased transcriptional activity and abnormal cellular localization as the molecular mechanisms for TBX6 missense loss-of-function alleles. Expanding the mutational spectrum of TBX6 pathogenic alleles enabled an increased molecular diagnostic detection rate, provided further evidence for the gene dosage-dependent genetic model underlying CS, and refined clinical classification.
Keywords: Alleles; Cell Line; Female; Gene Expression; Genes, Reporter; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inheritance Patterns; Male; Models, Molecular; Molecular Diagnostic Techniques; Mutation, Missense; Phenotype; Protein Conformation; Radiography; Sequence Analysis, DNA; Spine; Structure-Activity Relationship; T-Box Domain Proteins; Whole Exome Sequencing

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Whole Exome Sequencing; Wolff-Parkinson-White Syndrome; Young Adult

Biallelic mutations in valyl-tRNA synthetase gene VARS are associated with a progressive neurodevelopmental epileptic encephalopathy. - Friedman, Jennifer; Smith, Desiree E; Issa, Mahmoud Y; Stanley, Valentina; Wang, Rengang; Mendes, Marisa I; Wright, Meredith S; Wigby, Kristen; Hildreth, Amber; Crawford, John R; Koehler, Alanna E; Chowdhury, Shimul; et al. (Nat Commun, 2019)
Aminoacyl-tRNA synthetases (ARSs) function to transfer amino acids to cognate tRNA molecules, which are required for protein translation. To date, biallelic mutations in 31 ARS genes are known to cause recessive, early-onset severe multi-organ diseases. VARS encodes the only known valine cytoplasmic-localized aminoacyl-tRNA synthetase. Here, we report seven patients from five unrelated families with five different biallelic missense variants in VARS. Subjects present with a range of global developmental delay, epileptic encephalopathy and primary or progressive microcephaly. Longitudinal assessment demonstrates progressive cortical atrophy and white matter volume loss. Variants map to the VARS tRNA binding domain and adjacent to the anticodon domain, and disrupt highly conserved residues. Patient primary cells show intact VARS protein but reduced enzymatic activity, suggesting partial loss of function. The implication of VARS in pediatric neurodegeneration broadens the spectrum of human diseases due to mutations in tRNA synthetase genes.
Keywords: Alleles; Anticodon; Child; Child, Preschool; Disease Progression; Epilepsy; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Mutation; Neurodevelopmental Disorders; Pedigree; Protein Biosynthesis; Protein Interaction Domains and Motifs; RNA, Transfer; Valine-tRNA Ligase; Whole Exome Sequencing; Whole Genome Sequencing

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Yuan, Bo; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

COL4A1 mutations as a potential novel cause of autosomal dominant CAKUT in humans. - Kitzler, Thomas M; Schneider, Ronen; Kohl, Stefan; Kolvenbach, Caroline M; Connaughton, Dervla M; Dai, Rufeng; Mann, Nina; Nakayama, Makiko; Majmundar, Amar J; Wu, Chen-Han W; Kari, Jameela A; El Desoky, Sherif M; et al. (Hum Genet, 2019)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease (~ 45%) that manifests before 30 years of age. The genetic locus containing COL4A1 (13q33-34) has been implicated in vesicoureteral reflux (VUR), but mutations in COL4A1 have not been reported in CAKUT. We hypothesized that COL4A1 mutations cause CAKUT in humans. We performed whole exome sequencing (WES) in 550 families with CAKUT. As negative control cohorts we used WES sequencing data from patients with nephronophthisis (NPHP) with no genetic cause identified (n = 257) and with nephrotic syndrome (NS) due to monogenic causes (n = 100). We identified a not previously reported heterozygous missense variant in COL4A1 in three siblings with isolated VUR. When examining 549 families with CAKUT, we identified nine additional different heterozygous missense mutations in COL4A1 in 11 individuals from 11 unrelated families with CAKUT, while no COL4A1 mutations were identified in a control cohort with NPHP and only one in the cohort with NS. Most individuals (12/14) had isolated CAKUT with no extrarenal features. The predominant phenotype was VUR (9/14). There were no clinical features of the COL4A1-related disorders (e.g., HANAC syndrome, porencephaly, tortuosity of retinal arteries). Whereas COL4A1-related disorders are typically caused by glycine substitutions in the collagenous domain (84.4% of variants), only one variant in our cohort is a glycine substitution within the collagenous domain (1/10). We identified heterozygous COL4A1 mutations as a potential novel autosomal dominant cause of CAKUT that is allelic to the established COL4A1-related disorders and predominantly caused by non-glycine substitutions.
Keywords: Alleles; Amino Acid Substitution; Collagen Type IV; Computational Biology; Congenital Abnormalities; Databases, Genetic; DNA Mutational Analysis; Evolution, Molecular; Female; Genetic Association Studies; Genetic Loci; Genomics; Heterozygote; Humans; Kidney; Kidney Diseases, Cystic; Male; Mutation; Nephrotic Syndrome; Phenotype; Urinary Tract; Web Browser; Whole Exome Sequencing

Contribution of noncoding pathogenic variants to RPGRIP1-mediated inherited retinal degeneration. - Jamshidi, Farzad; Place, Emily M; Mehrotra, Sudeep; Navarro-Gomez, Daniel; Maher, Mathew; Branham, Kari E; Valkanas, Elise; Cherry, Timothy J; Lek, Monkol; Macarthur, Daniel; Pierce, Eric A; Bujakowska, Kinga M (Genet Med, 2019)
PURPOSE: With the advent of gene therapies for inherited retinal degenerations (IRDs), genetic diagnostics will have an increasing role in clinical decision-making. Yet the genetic cause of disease cannot be identified using exon-based sequencing for a significant portion of patients. We hypothesized that noncoding pathogenic variants contribute significantly to the genetic causality of IRDs and evaluated patients with single coding pathogenic variants in RPGRIP1 to test this hypothesis. METHODS: IRD families underwent targeted panel sequencing. Unsolved cases were explored by exome and genome sequencing looking for additional pathogenic variants. Candidate pathogenic variants were then validated by Sanger sequencing, quantitative polymerase chain reaction, and in vitro splicing assays in two cell lines analyzed through amplicon sequencing. RESULTS: Among 1722 families, 3 had biallelic loss-of-function pathogenic variants in RPGRIP1 while 7 had a single disruptive coding pathogenic variants. Exome and genome sequencing revealed potential noncoding pathogenic variants in these 7 families. In 6, the noncoding pathogenic variants were shown to lead to loss of function in vitro. CONCLUSION: Noncoding pathogenic variants were identified in 6 of 7 families with single coding pathogenic variants in RPGRIP1. The results suggest that noncoding pathogenic variants contribute significantly to the genetic causality of IRDs and RPGRIP1-mediated IRDs are more common than previously thought.
Keywords: Adult; Chromosome Mapping; DNA Mutational Analysis; DNA, Intergenic; Female; HEK293 Cells; Humans; Male; Mutation; Pedigree; Proteins; Retinal Degeneration; Whole Exome Sequencing; Whole Genome Sequencing

Exploring by whole exome sequencing patients with initial diagnosis of Rubinstein-Taybi syndrome: the interconnections of epigenetic machinery disorders. - Negri, Gloria; Magini, Pamela; Milani, Donatella; Crippa, Milena; Biamino, Elisa; Piccione, Maria; Sotgiu, Stefano; Perrìa, Chiara; Vitiello, Giuseppina; Frontali, Marina; Boni, Antonella; Di Fede, Elisabetta; et al. (Hum Genet, 2019)
Rubinstein-Taybi syndrome (RSTS) is an autosomal-dominant neurodevelopmental disease affecting 1:125,000 newborns characterized by intellectual disability, growth retardation, facial dysmorphisms and skeletal abnormalities. RSTS is caused by mutations in genes encoding for writers of the epigenetic machinery: CREBBP (~ 60%) or its homologous EP300 (~ 10%). No causative mutation is identified in up to 30% of patients. We performed whole-exome sequencing (WES) on eight RSTS-like individuals who had normal high-resolution array CGH testing and were CREBBP- and EP300-mutation -negative, to identify the molecular cause. In four cases, we identified putatively causal variants in three genes (ASXL1, KMT2D and KMT2A) encoding members of the epigenetic machinery known to be associated with the Bohring-Opitz, Kabuki and Wiedemann-Steiner syndromes. Each variant is novel, de novo, fulfills the ACMG criteria and is predicted to result in loss-of-function leading to haploinsufficiency of the epi-gene. In two of the remaining cases, homozygous/compound heterozygous variants in XYLT2 and PLCB4 genes, respectively, associated with spondyloocular and auriculocondylar 2 syndromes and in the latter an additional candidate variant in XRN2, a gene yet unrelated to any disease, were detected, but their pathogenicity remains uncertain. These results underscore the broad clinical spectrum of Mendelian disorders of the epigenetic apparatus and the high rate of WES disclosure of the genetic basis in cases which may pose a challenge for phenotype encompassing distinct syndromes. The overlapping features of distinct intellectual disability syndromes reflect common pathogenic molecular mechanisms affecting the complex regulation of balance between open and closed chromatin.
Keywords: Child; Child, Preschool; Comparative Genomic Hybridization; CREB-Binding Protein; E1A-Associated p300 Protein; Epigenesis, Genetic; Facies; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mutation; Phenotype; Rubinstein-Taybi Syndrome; Whole Exome Sequencing

Identification and association of recurrent ALOXE3 mutation with non-bullous congenital ichthyosiform erythroderma in two ethnically distinct Pakistani families. - Rahman, Simeen Ber; Mir, Asif; Ahmad, Nafees; Haider, Syed Husnain; Malik, Salman Akbar; Nasir, Muhammad (Congenit Anom (Kyoto), 2019)
Non-bullous congenital ichthyosiform erythroderma (NCIE) is characterized by skin scaling with erythema. In this study, two Pakistani families with NCIE are genetically characterized through Whole Exome and Sanger sequencing to identify molecular basis of the disease. We identified a nonsense homozygous c.2026C>T mutation of ALOXE3, causing premature termination of the eLOX3 protein (p.Q676X). In silico studies predicted impaired enzymatic activity of the premature truncated eLOX3, leading to abnormal synthesis of specific hepoxilin derivatives, essential for epidermal barrier formation. It is the first ever study reporting homozygotes of p.Q676X mutation in ethnically distinct two Pakistani families; otherwise, heterozygotes of the said mutation have been reported in South Asian population only. Hence, mutation seems to be region-specific and may be useful for molecular diagnosis of NCIE. Moreover, our findings should help in genetic counseling and career screening.
Keywords: 8,11,14-Eicosatrienoic Acid; Adolescent; Adult; Base Sequence; Case-Control Studies; Child; Child, Preschool; Codon, Nonsense; Ethnic Groups; Female; Flavanones; Gene Expression; Homozygote; Humans; Ichthyosis, Lamellar; Lipoxygenase; Male; Middle Aged; Molecular Docking Simulation; Pakistan; Pedigree; Protein Binding; Protein Structure, Secondary; Skin; Whole Exome Sequencing

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States; Whole Exome Sequencing

Loss of function, missense, and intronic variants in NOTCH1 confer different risks for left ventricular outflow tract obstructive heart defects in two European cohorts. - Helle, Emmi; Córdova-Palomera, Aldo; Ojala, Tiina; Saha, Priyanka; Potiny, Praneetha; Gustafsson, Stefan; Ingelsson, Erik; Bamshad, Michael; Nickerson, Deborah; Chong, Jessica X; Ashley, Euan; Priest, James R (Genet Epidemiol, 2019)
Loss of function variants in NOTCH1 cause left ventricular outflow tract obstructive defects (LVOTO). However, the risk conferred by rare and noncoding variants in NOTCH1 for LVOTO remains largely uncharacterized. In a cohort of 49 families affected by hypoplastic left heart syndrome, a severe form of LVOTO, we discovered predicted loss of function NOTCH1 variants in 6% of individuals. Rare or low-frequency missense variants were found in 16% of families. To make a quantitative estimate of the genetic risk posed by variants in NOTCH1 for LVOTO, we studied associations of 400 coding and noncoding variants in NOTCH1 in 1,085 cases and 332,788 controls from the UK Biobank. Two rare intronic variants in strong linkage disequilibrium displayed significant association with risk for LVOTO amongst European-ancestry individuals. This result was replicated in an independent analysis of 210 cases and 68,762 controls of non-European and mixed ancestry. In conclusion, carrying rare predicted loss of function variants in NOTCH1 confer significant risk for LVOTO. In addition, the two intronic variants seem to be associated with an increased risk for these defects. Our approach demonstrates the utility of population-based data sets in quantifying the specific risk of individual variants for disease-related phenotypes.
Keywords: Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Introns; Loss of Function Mutation; Male; Mutation, Missense; Pedigree; Receptor, Notch1; Risk Factors; Ventricular Outflow Obstruction; Whole Exome Sequencing

Reanalysis of Clinical Exome Sequencing Data. - Liu, Pengfei; Meng, Linyan; Normand, Elizabeth A; Xia, Fan; Song, Xiaofei; Ghazi, Andrew; Rosenfeld, Jill; Magoulas, Pilar L; Braxton, Alicia; Ward, Patricia; Dai, Hongzheng; Yuan, Bo; et al. (N Engl J Med, 2019)
Keywords: Exome; Genetic Diseases, Inborn; Genetic Testing; Humans; Mutation; Phenotype; Sequence Analysis, DNA; Whole Exome Sequencing

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly. - Ullah, Irfan; Kakar, Naseebullah; Schrauwen, Isabelle; Hussain, Shabir; Chakchouk, Imen; Liaqat, Khurram; Acharya, Anushree; Wasif, Naveed; Santos-Cortez, Regie Lyn P; Khan, Saadullah; Aziz, Abdul; Lee, Kwanghyuk; et al. (Hum Genet, 2019)
Postaxial polydactyly (PAP) is a common limb malformation that often leads to cosmetic and functional complications. Molecular evaluation of polydactyly can serve as a tool to elucidate genetic and signaling pathways that regulate limb development, specifically, the anterior-posterior specification of the limb. To date, only five genes have been identified for nonsyndromic PAP: FAM92A, GLI1, GLI3, IQCE and ZNF141. In this study, two Pakistani multiplex consanguineous families with autosomal recessive nonsyndromic PAP were clinically and molecularly evaluated. From both pedigrees, a DNA sample from an affected member underwent exome sequencing. In each family, we identified a segregating frameshift (c.591dupA [p.(Q198Tfs*21)]) and nonsense variant (c.2173A > T [p.(K725*)]) in KIAA0825 (also known as C5orf36). Although KIAA0825 encodes a protein of unknown function, it has been demonstrated that its murine ortholog is expressed during limb development. Our data contribute to the establishment of a catalog of genes important in limb patterning, which can aid in diagnosis and obtaining a better understanding of the biology of polydactyly.
Keywords: Animals; Consanguinity; Family Health; Female; Fingers; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice, Inbred C57BL; Mutation; Pedigree; Phenotype; Polydactyly; Toes; Whole Exome Sequencing

Whole-Exome Sequencing Enables a Precision Medicine Approach for Kidney Transplant Recipients. - Mann, Nina; Braun, Daniela A; Amann, Kassaundra; Tan, Weizhen; Shril, Shirlee; Connaughton, Dervla M; Nakayama, Makiko; Schneider, Ronen; Kitzler, Thomas M; van der Ven, Amelie T; Chen, Jing; Ityel, Hadas; et al. (J Am Soc Nephrol, 2019)
BACKGROUND: Whole-exome sequencing (WES) finds a CKD-related mutation in approximately 20% of patients presenting with CKD before 25 years of age. Although provision of a molecular diagnosis could have important implications for clinical management, evidence is lacking on the diagnostic yield and clinical utility of WES for pediatric renal transplant recipients. METHODS: To determine the diagnostic yield of WES in pediatric kidney transplant recipients, we recruited 104 patients who had received a transplant at Boston Children's Hospital from 2007 through 2017, performed WES, and analyzed results for likely deleterious variants in approximately 400 genes known to cause CKD. RESULTS: By WES, we identified a genetic cause of CKD in 34 out of 104 (32.7%) transplant recipients. The likelihood of detecting a molecular genetic diagnosis was highest for patients with urinary stone disease (three out of three individuals), followed by renal cystic ciliopathies (seven out of nine individuals), steroid-resistant nephrotic syndrome (nine out of 21 individuals), congenital anomalies of the kidney and urinary tract (ten out of 55 individuals), and chronic glomerulonephritis (one out of seven individuals). WES also yielded a molecular diagnosis for four out of nine individuals with ESRD of unknown etiology. The WES-related molecular genetic diagnosis had implications for clinical care for five patients. CONCLUSIONS: Nearly one third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES. Knowledge of this genetic information can help guide management of both transplant patients and potential living related donors.
Keywords: Adolescent; Boston; Child; Child, Preschool; Cohort Studies; Female; Genetic Predisposition to Disease; Genetic Testing; Graft Rejection; Graft Survival; Hospitals, Pediatric; Humans; Kidney Transplantation; Male; Precision Medicine; Prognosis; Renal Insufficiency, Chronic; Retrospective Studies; Risk Assessment; Severity of Illness Index; Survival Analysis; Transplant Recipients; Treatment Outcome; Whole Exome Sequencing

Analysis of 17 genes detects mutations in 81% of 811 patients with lissencephaly. - Di Donato, Nataliya; Timms, Andrew E; Aldinger, Kimberly A; Mirzaa, Ghayda M; Bennett, James T; Collins, Sarah; Olds, Carissa; Mei, Davide; Chiari, Sara; Carvill, Gemma; Myers, Candace T; Rivière, Jean-Baptiste; et al. (Genet Med, 2018)
PURPOSE: To estimate diagnostic yield and genotype-phenotype correlations in a cohort of 811 patients with lissencephaly or subcortical band heterotopia. METHODS: We collected DNA from 756 children with lissencephaly over 30 years. Many were tested for deletion 17p13.3 and mutations of LIS1, DCX, and ARX, but few other genes. Among those tested, 216 remained unsolved and were tested by a targeted panel of 17 genes (ACTB, ACTG1, ARX, CRADD, DCX, LIS1, TUBA1A, TUBA8, TUBB2B, TUBB, TUBB3, TUBG1, KIF2A, KIF5C, DYNC1H1, RELN, and VLDLR) or by whole-exome sequencing. Fifty-five patients studied at another institution were added as a validation cohort. RESULTS: The overall mutation frequency in the entire cohort was 81%. LIS1 accounted for 40% of patients, followed by DCX (23%), TUBA1A (5%), and DYNC1H1 (3%). Other genes accounted for 1% or less of patients. Nineteen percent remained unsolved, which suggests that several additional genes remain to be discovered. The majority of unsolved patients had posterior pachygyria, subcortical band heterotopia, or mild frontal pachygyria. CONCLUSION: The brain-imaging pattern correlates with mutations in single lissencephaly-associated genes, as well as in biological pathways. We propose the first LIS classification system based on the underlying molecular mechanisms.
Keywords: Brain; Classical Lissencephalies and Subcortical Band Heterotopias; DNA Mutational Analysis; Female; Genetic Association Studies; Humans; Lissencephaly; Male; Mutation; Whole Exome Sequencing

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Doddapaneni, Harsha; Hu, Jianhong; Muzny, Donna M; Guven, Yeliz; Aktoren, Oya; Kayserili, Hülya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface; Whole Exome Sequencing

Confirmation of the Role of DHX38 in the Etiology of Early-Onset Retinitis Pigmentosa. - Latif, Zahid; Chakchouk, Imen; Schrauwen, Isabelle; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Abbe, Izoduwa; Acharya, Anushree; Jarral, Afeefa; Ali, Imran; Ullah, Ehsan; Khan, Muhammad Nasim; Ali, Ghazanfar; et al. (Invest Ophthalmol Vis Sci, 2018)
Purpose: Retinitis pigmentosa (RP) is a genetically heterogeneous trait with autosomal-recessive (ar) inheritance underlying 50% of genetic disease cases. Sixty-one arRP genes have been identified, and recently, DHX38 has been reported as a potential candidate gene for arRP with only a single family reported with a variant of unknown significance. We identified a missense variant in DHX38 that co-segregates with the arRP phenotype in two Pakistani families confirming the involvement of DHX38 in the etiology of early-onset RP. Methods: Exome sequencing was performed using two DNA samples from affected members of Pakistani families (MA88 and MA157) with early onset arRP. Sanger sequencing of DNA samples from all family members confirmed the segregation of candidate variant within both families. Results: A novel missense DHX38 variant c.971G>A; p.(Arg324Gln) was identified which segregates with the arRP phenotype and yielded a logarithm of the odds (LOD) score of 5.0 and 4.3 for families MA88 and MA157, respectively. This variant is predicted to be conserved and deleterious by several bioinformatics tools. Conclusions: We identified a second deleterious DHX38 variant that segregates with arRP in two families, providing additional evidence that DHX38 is involved in RP etiology. DHX38 encodes for pre-mRNA splicing factor PRP16, which is important in catalyzing pre-mRNA splicing.
Keywords: Adolescent; Adult; Cataract; Computational Biology; DEAD-box RNA Helicases; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; Humans; Male; Mutation, Missense; Nucleotide Mapping; Ophthalmoscopy; Pedigree; Retinitis Pigmentosa; RNA Splicing Factors; Sequence Analysis, DNA; Whole Exome Sequencing; Young Adult

De novo variants in congenital diaphragmatic hernia identify MYRF as a new syndrome and reveal genetic overlaps with other developmental disorders. - Qi, Hongjian; Yu, Lan; Zhou, Xueya; Wynn, Julia; Zhao, Haoquan; Guo, Yicheng; Zhu, Na; Kitaygorodsky, Alexander; Hernan, Rebecca; Aspelund, Gudrun; Lim, Foong-Yen; Crombleholme, Timothy; et al. (PLoS Genet, 2018)
Congenital diaphragmatic hernia (CDH) is a severe birth defect that is often accompanied by other congenital anomalies. Previous exome sequencing studies for CDH have supported a role of de novo damaging variants but did not identify any recurrently mutated genes. To investigate further the genetics of CDH, we analyzed de novo coding variants in 362 proband-parent trios including 271 new trios reported in this study. We identified four unrelated individuals with damaging de novo variants in MYRF (P = 5.3x10(-8)), including one likely gene-disrupting (LGD) and three deleterious missense (D-mis) variants. Eight additional individuals with de novo LGD or missense variants were identified from our other genetic studies or from the literature. Common phenotypes of MYRF de novo variant carriers include CDH, congenital heart disease and genitourinary abnormalities, suggesting that it represents a novel syndrome. MYRF is a membrane associated transcriptional factor highly expressed in developing diaphragm and is depleted of LGD variants in the general population. All de novo missense variants aggregated in two functional protein domains. Analyzing the transcriptome of patient-derived diaphragm fibroblast cells suggest that disease associated variants abolish the transcription factor activity. Furthermore, we showed that the remaining genes with damaging variants in CDH significantly overlap with genes implicated in other developmental disorders. Gene expression patterns and patient phenotypes support pleiotropic effects of damaging variants in these genes on CDH and other developmental disorders. Finally, functional enrichment analysis implicates the disruption of regulation of gene expression, kinase activities, intra-cellular signaling, and cytoskeleton organization as pathogenic mechanisms in CDH.
Keywords: Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Female; Genetic Variation; Heart Defects, Congenital; Hernias, Diaphragmatic, Congenital; Humans; Infant, Newborn; Longitudinal Studies; Male; Membrane Proteins; Mutation; Mutation, Missense; Phenotype; Sequence Analysis, RNA; Syndrome; Transcription Factors; Whole Exome Sequencing; Whole Genome Sequencing

Detection of variants in dystroglycanopathy-associated genes through the application of targeted whole-exome sequencing analysis to a large cohort of patients with unexplained limb-girdle muscle weakness. - Johnson, Katherine; Bertoli, Marta; Phillips, Lauren; Topf, Ana; Van den Bergh, Peter; Vissing, John; Witting, Nanna; Nafissi, Shahriar; Jamal-Omidi, Shirin; Łusakowska, Anna; Kostera-Pruszczyk, Anna; Potulska-Chromik, Anna; et al. (Skelet Muscle, 2018)
BACKGROUND: Dystroglycanopathies are a clinically and genetically heterogeneous group of disorders that are typically characterised by limb-girdle muscle weakness. Mutations in 18 different genes have been associated with dystroglycanopathies, the encoded proteins of which typically modulate the binding of α-dystroglycan to extracellular matrix ligands by altering its glycosylation. This results in a disruption of the structural integrity of the myocyte, ultimately leading to muscle degeneration. METHODS: Deep phenotypic information was gathered using the PhenoTips online software for 1001 patients with unexplained limb-girdle muscle weakness from 43 different centres across 21 European and Middle Eastern countries. Whole-exome sequencing with at least 250 ng DNA was completed using an Illumina exome capture and a 38 Mb baited target. Genes known to be associated with dystroglycanopathies were analysed for disease-causing variants. RESULTS: Suspected pathogenic variants were detected in DPM3, ISPD, POMT1 and FKTN in one patient each, in POMK in two patients, in GMPPB in three patients, in FKRP in eight patients and in POMT2 in ten patients. This indicated a frequency of 2.7% for the disease group within the cohort of 1001 patients with unexplained limb-girdle muscle weakness. The phenotypes of the 27 patients were highly variable, yet with a fundamental presentation of proximal muscle weakness and elevated serum creatine kinase. CONCLUSIONS: Overall, we have identified 27 patients with suspected pathogenic variants in dystroglycanopathy-associated genes. We present evidence for the genetic and phenotypic diversity of the dystroglycanopathies as a disease group, while also highlighting the advantage of incorporating next-generation sequencing into the diagnostic pathway of rare diseases.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Dystroglycans; Female; Genetic Predisposition to Disease; Genetic Variation; Glycosylation; Heterozygote; Homozygote; Humans; Male; Middle Aged; Muscle Proteins; Muscular Dystrophies, Limb-Girdle; Mutation; Phenotype; Whole Exome Sequencing; Young Adult

Expanding the genetic architecture and phenotypic spectrum in the skeletal ciliopathies. - Zhang, Wenjuan; Taylor, S Paige; Ennis, Hayley A; Forlenza, Kimberly N; Duran, Ivan; Li, Bing; Sanchez, Jorge A Ortiz; Nevarez, Lisette; Nickerson, Deborah A; Bamshad, Michael; Lachman, Ralph S; Krakow, Deborah; et al. (Hum Mutat, 2018)
Defects in the biosynthesis and/or function of primary cilia cause a spectrum of disorders collectively referred to as ciliopathies. A subset of these disorders is distinguished by profound abnormalities of the skeleton that include a long narrow chest with markedly short ribs, extremely short limbs, and polydactyly. These include the perinatal lethal short-rib polydactyly syndromes (SRPS) and the less severe asphyxiating thoracic dystrophy (ATD), Ellis-van Creveld (EVC) syndrome, and cranioectodermal dysplasia (CED) phenotypes. To identify new genes and define the spectrum of mutations in the skeletal ciliopathies, we analyzed 152 unrelated families with SRPS, ATD, and EVC. Causal variants were discovered in 14 genes in 120 families, including one newly associated gene and two genes previously associated with other ciliopathies. These three genes encode components of three different ciliary complexes; FUZ, which encodes a planar cell polarity complex molecule; TRAF3IP1, which encodes an anterograde ciliary transport protein; and LBR, which encodes a nuclear membrane protein with sterol reductase activity. The results established the molecular basis of SRPS type IV, in which mutations were identified in four different ciliary genes. The data provide systematic insight regarding the genotypes associated with a large cohort of these genetically heterogeneous phenotypes and identified new ciliary components required for normal skeletal development.
Keywords: Ciliopathies; Cytoplasmic Dyneins; Genetic Association Studies; Genetic Markers; Genetic Variation; Genotype; Humans; Mutation; Phenotype; Proteins; Radiography; Skeleton; Whole Exome Sequencing

Genotype-phenotype investigation of 35 patients from 11 unrelated families with camptodactyly-arthropathy-coxa vara-pericarditis (CACP) syndrome. - Yilmaz, Saliha; Uludağ Alkaya, Dilek; Kasapcopur, Ozgur; Barut, Kenan; Akdemir, Ekin S; Celen, Cemre; Youngblood, Mark W; Yasuno, Katsuhito; Bilguvar, Kaya; Günel, Murat; Tuysuz, Beyhan (Mol Genet Genomic Med, 2018)
BACKGROUND: The camptodactyly-arthropathy-coxa vara-pericarditis syndrome (CACP) is a rare autosomal recessive condition characterized by camptodactyly, noninflammatory arthropathy, coxa vara, and pericarditis. CACP is caused by mutations in the proteoglycan 4 (PRG4) gene, which encodes a lubricating glycoprotein present in the synovial fluid and at the surface of articular cartilage. METHODS: In the present study, we compared the clinical and molecular findings of CACP syndrome in 35 patients from 11 unrelated families. In 28 patients, whole exome sequencing was used to investigate genomic variations. RESULTS: We found that camptodactyly of hands was the first symptom presented by most patients. Swelling of wrists, knees, and elbows began before 4 years of age, while the age of joint involvement was variable. Patients reported an increased pain level after the age of 10, and severe hip involvement developed after 20 years old. All patients presented developmental coxa vara and seven patients (~22%) had pleural effusion, pericarditis, and/or ascites. We identified nine novel genomic alterations, including the first case of homozygous complete deletion of exon 1 in the PRG4 gene. CONCLUSION: With this study, we contribute to the catalog of CACP causing variants. We confirm that the skeletal component of this disease worsens with age, and presents the potential mechanisms for interfamily variability, by discussing the influence of a modifier gene and escape from nonsense-mediated mRNA decay. We believe that this report will increase awareness of this familial arthropathic condition and the characteristic clinical and radiological findings will facilitate the differentiation from the common childhood rheumatic diseases such as juvenile idiopathic arthritis.
Keywords: Adolescent; Adult; Arthropathy, Neurogenic; Child; Child, Preschool; Coxa Vara; Exons; Female; Genetic Association Studies; Hand Deformities, Congenital; Humans; Male; Middle Aged; Mutation; Proteoglycans; Retrospective Studies; Sequence Deletion; Synovitis; Whole Exome Sequencing

Monoallelic Mutations to DNAJB11 Cause Atypical Autosomal-Dominant Polycystic Kidney Disease. - Cornec-Le Gall, Emilie; Olson, Rory J; Besse, Whitney; Heyer, Christina M; Gainullin, Vladimir G; Smith, Jessica M; Audrézet, Marie-Pierre; Hopp, Katharina; Porath, Binu; Shi, Beili; Baheti, Saurabh; Senum, Sarah R; et al. (Am J Hum Genet, 2018)
Autosomal-dominant polycystic kidney disease (ADPKD) is characterized by the progressive development of kidney cysts, often resulting in end-stage renal disease (ESRD). This disorder is genetically heterogeneous with ∼7% of families genetically unresolved. We performed whole-exome sequencing (WES) in two multiplex ADPKD-like pedigrees, and we analyzed a further 591 genetically unresolved, phenotypically similar families by targeted next-generation sequencing of 65 candidate genes. WES identified a DNAJB11 missense variant (p.Pro54Arg) in two family members presenting with non-enlarged polycystic kidneys and a frameshifting change (c.166_167insTT) in a second family with small renal and liver cysts. DNAJB11 is a co-factor of BiP, a key chaperone in the endoplasmic reticulum controlling folding, trafficking, and degradation of secreted and membrane proteins. Five additional multigenerational families carrying DNAJB11 mutations were identified by the targeted analysis. The clinical phenotype was consistent in the 23 affected members, with non-enlarged cystic kidneys that often evolved to kidney atrophy; 7 subjects reached ESRD from 59 to 89 years. The lack of kidney enlargement, histologically evident interstitial fibrosis in non-cystic parenchyma, and recurring episodes of gout (one family) suggested partial phenotypic overlap with autosomal-dominant tubulointerstitial diseases (ADTKD). Characterization of DNAJB11-null cells and kidney samples from affected individuals revealed a pathogenesis associated with maturation and trafficking defects involving the ADPKD protein, PC1, and ADTKD proteins, such as UMOD. DNAJB11-associated disease is a phenotypic hybrid of ADPKD and ADTKD, characterized by normal-sized cystic kidneys and progressive interstitial fibrosis resulting in late-onset ESRD.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Amino Acid Sequence; Base Sequence; Epithelial Cells; Family; Female; HSP40 Heat-Shock Proteins; Humans; Loop of Henle; Male; Middle Aged; Mutation; Pedigree; Polycystic Kidney, Autosomal Dominant; TRPP Cation Channels; Uromodulin; Whole Exome Sequencing; Young Adult

Mutations in the Epithelial Cadherin-p120-Catenin Complex Cause Mendelian Non-Syndromic Cleft Lip with or without Cleft Palate. - Cox, Liza L; Cox, Timothy C; Moreno Uribe, Lina M; Zhu, Ying; Richter, Chika T; Nidey, Nichole; Standley, Jennifer M; Deng, Mei; Blue, Elizabeth; Chong, Jessica X; Yang, Yueqin; Carstens, Russ P; et al. (Am J Hum Genet, 2018)
Non-syndromic cleft lip with or without cleft palate (NS-CL/P) is one of the most common human birth defects and is generally considered a complex trait. Despite numerous loci identified by genome-wide association studies, the effect sizes of common variants are relatively small, with much of the presumed genetic contribution remaining elusive. We report exome-sequencing results in 209 people from 72 multi-affected families with pedigree structures consistent with autosomal-dominant inheritance and variable penetrance. Herein, pathogenic variants are described in four genes encoding components of the p120-catenin complex (CTNND1, PLEKHA7, PLEKHA5) and an epithelial splicing regulator (ESRP2), in addition to the known CL/P-associated gene, CDH1, which encodes E-cadherin. The findings were also validated in a second cohort of 497 people with NS-CL/P, comprising small families and singletons with pathogenic variants in these genes identified in 14% of multi-affected families and 2% of the replication cohort of smaller families. Enriched expression of each gene/protein in human and mouse embryonic oro-palatal epithelia, demonstration of functional impact of CTNND1 and ESRP2 variants, and recapitulation of the CL/P spectrum in Ctnnd1 knockout mice support a causative role in CL/P pathogenesis. These data show that primary defects in regulators of epithelial cell adhesion are the most significant contributors to NS-CL/P identified to date and that inherited and de novo single gene variants explain a substantial proportion of NS-CL/P.
Keywords: Alleles; Amino Acid Sequence; Animals; Biotinylation; Cadherins; Catenins; Cleft Lip; Cleft Palate; Epithelium; Female; Gene Deletion; Genetic Predisposition to Disease; Humans; Infant; Infant, Newborn; Male; Mice; Mutation; Palate; Pedigree; Syndrome; Whole Exome Sequencing

A variant in LMX1A causes autosomal recessive severe-to-profound hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Liaqat, Khurram; Jan, Abid; Nasir, Abdul; Hussain, Shabir; Nickerson, Deborah A; Bamshad, Michael J; Ullah, Asmat; Ahmad, Wasim; Leal, Suzanne M (Hum Genet, 2018)
Hereditary hearing impairment is a common sensory disorder that is genetically and phenotypically heterogeneous. In this study, we used a homozygosity mapping and exome sequencing strategy to study a consanguineous Pakistani family with autosomal recessive severe-to-profound hearing impairment. This led to the identification of a missense variant (p.Ile369Thr) in the LMX1A gene affecting a conserved residue in the C-terminus of the protein, which was predicted damaging by an in silico bioinformatics analysis. The p.Ile369Thr variant disrupts several C-terminal and homeodomain residue interactions, including an interaction with homeodomain residue p.Val241 that was previously found to be involved in autosomal dominant progressive HI. LIM-homeodomain factor Lmx1a is expressed in the inner ear through development, shows a progressive restriction to non-sensory epithelia, and is important in the separation of the sensory and non-sensory domains in the inner ear. Homozygous Lmx1a mutant mice (Dreher) are deaf with dysmorphic ears with an abnormal morphogenesis and fused and misshapen sensory organs; however, computed tomography performed on a hearing-impaired family member did not reveal any cochleovestibular malformations. Our results suggest that LMX1A is involved in both human autosomal recessive and dominant sensorineural hearing impairment.
Keywords: Adolescent; Adult; Animals; Child; Disease Models, Animal; Ear, Inner; Female; Genes, Dominant; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; LIM-Homeodomain Proteins; Male; Mice; Mutation, Missense; Pedigree; Transcription Factors; Whole Exome Sequencing

Whole exome sequencing analysis in severe chronic obstructive pulmonary disease. - Qiao, Dandi; Ameli, Asher; Prokopenko, Dmitry; Chen, Han; Kho, Alvin T; Parker, Margaret M; Morrow, Jarrett; Hobbs, Brian D; Liu, Yanhong; Beaty, Terri H; Crapo, James D; Barnes, Kathleen C; et al. (Hum Mol Genet, 2018)
Chronic obstructive pulmonary disease (COPD), one of the leading causes of death worldwide, is substantially influenced by genetic factors. Alpha-1 antitrypsin deficiency demonstrates that rare coding variants of large effect can influence COPD susceptibility. To identify additional rare coding variants in patients with severe COPD, we conducted whole exome sequencing analysis in 2543 subjects from two family-based studies (Boston Early-Onset COPD Study and International COPD Genetics Network) and one case-control study (COPDGene). Applying a gene-based segregation test in the family-based data, we identified significant segregation of rare loss of function variants in TBC1D10A and RFPL1 (P-value < 2x10-6), but were unable to find similar variants in the case-control study. In single-variant, gene-based and pathway association analyses, we were unable to find significant findings that replicated or were significant in meta-analysis. However, we found that the top results in the two datasets were in proximity to each other in the protein-protein interaction network (P-value = 0.014), suggesting enrichment of these results for similar biological processes. A network of these association results and their neighbors was significantly enriched in the transforming growth factor beta-receptor binding and cilia-related pathways. Finally, in a more detailed examination of candidate genes, we identified individuals with putative high-risk variants, including patients harboring homozygous mutations in genes associated with cutis laxa and Niemann-Pick Disease Type C. Our results likely reflect heterogeneity of genetic risk for COPD along with limitations of statistical power and functional annotation, and highlight the potential of network analysis to gain insight into genetic association studies.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; DNA Mutational Analysis; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Whole Exome Sequencing; Young Adult

Whole exome sequencing frequently detects a monogenic cause in early onset nephrolithiasis and nephrocalcinosis. - Daga, Ankana; Majmundar, Amar J; Braun, Daniela A; Gee, Heon Yung; Lawson, Jennifer A; Shril, Shirlee; Jobst-Schwan, Tilman; Vivante, Asaf; Schapiro, David; Tan, Weizhen; Warejko, Jillian K; Widmeier, Eugen; et al. (Kidney Int, 2018)
The incidence of nephrolithiasis continues to rise. Previously, we showed that a monogenic cause could be detected in 11.4% of individuals with adult-onset nephrolithiasis or nephrocalcinosis and in 16.7-20.8% of individuals with onset before 18 years of age, using gene panel sequencing of 30 genes known to cause nephrolithiasis/nephrocalcinosis. To overcome the limitations of panel sequencing, we utilized whole exome sequencing in 51 families, who presented before age 25 years with at least one renal stone or with a renal ultrasound finding of nephrocalcinosis to identify the underlying molecular genetic cause of disease. In 15 of 51 families, we detected a monogenic causative mutation by whole exome sequencing. A mutation in seven recessive genes (AGXT, ATP6V1B1, CLDN16, CLDN19, GRHPR, SLC3A1, SLC12A1), in one dominant gene (SLC9A3R1), and in one gene (SLC34A1) with both recessive and dominant inheritance was detected. Seven of the 19 different mutations were not previously described as disease-causing. In one family, a causative mutation in one of 117 genes that may represent phenocopies of nephrolithiasis-causing genes was detected. In nine of 15 families, the genetic diagnosis may have specific implications for stone management and prevention. Several factors that correlated with the higher detection rate in our cohort were younger age at onset of nephrolithiasis/nephrocalcinosis, presence of multiple affected members in a family, and presence of consanguinity. Thus, we established whole exome sequencing as an efficient approach toward a molecular genetic diagnosis in individuals with nephrolithiasis/nephrocalcinosis who manifest before age 25 years.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Disease Progression; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Heredity; Humans; Infant; Male; Mutation; Nephrocalcinosis; Nephrolithiasis; Pedigree; Phenotype; Predictive Value of Tests; Prognosis; Risk Factors; Tomography, X-Ray Computed; Ultrasonography; Whole Exome Sequencing; Young Adult

Whole Exome Sequencing Reveals a Monogenic Cause of Disease in ≈43% of 35 Families With Midaortic Syndrome. - Warejko, Jillian K; Schueler, Markus; Vivante, Asaf; Tan, Weizhen; Daga, Ankana; Lawson, Jennifer A; Braun, Daniela A; Shril, Shirlee; Amann, Kassaundra; Somers, Michael J G; Rodig, Nancy M; Baum, Michelle A; et al. (Hypertension, 2018)
Midaortic syndrome (MAS) is a rare cause of severe childhood hypertension characterized by narrowing of the abdominal aorta in children and is associated with extensive vascular disease. It may occur as part of a genetic syndrome, such as neurofibromatosis, or as consequence of a pathological inflammatory disease. However, most cases are considered idiopathic. We hypothesized that in a high percentage of these patients, a monogenic cause of disease may be detected by evaluating whole exome sequencing data for mutations in 1 of 38 candidate genes previously described to cause vasculopathy. We studied a cohort of 36 individuals from 35 different families with MAS by exome sequencing. In 15 of 35 families (42.9%), we detected likely causal dominant mutations. In 15 of 35 (42.9%) families with MAS, whole exome sequencing revealed a mutation in one of the genes previously associated with vascular disease (, , , , and ). Ten of the 15 mutations have not previously been reported. This is the first report of , , or mutations in individuals with MAS. Mutations were detected in (6/15 families), (4/15 families), (3/15 families), and one family each for and Eight individuals had syndromic disease and 7 individuals had isolated MAS. Whole exome sequencing can provide conclusive molecular genetic diagnosis in a high fraction of individuals with syndromic or isolated MAS. Establishing an etiologic diagnosis may reveal genotype/phenotype correlations for MAS in the future and should, therefore, be performed routinely in MAS.
Keywords: Adolescent; Aorta, Abdominal; Aortic Valve Stenosis; Child; Child, Preschool; Cohort Studies; Female; Genetic Association Studies; Humans; Hypertension; Jagged-1 Protein; Male; Mutation; Neurofibromatoses; Neurofibromin 1; Pedigree; Syndrome; United States; Whole Exome Sequencing

Whole-Exome Sequencing Identifies Novel Variants for Tooth Agenesis. - Dinckan, N; Du, R; Petty, L E; Coban-Akdemir, Z; Jhangiani, S N; Paine, I; Baugh, E H; Erdem, A P; Kayserili, H; Doddapaneni, H; Hu, J; Muzny, D M; et al. (J Dent Res, 2018)
Tooth agenesis is a common craniofacial abnormality in humans and represents failure to develop 1 or more permanent teeth. Tooth agenesis is complex, and variations in about a dozen genes have been reported as contributing to the etiology. Here, we combined whole-exome sequencing, array-based genotyping, and linkage analysis to identify putative pathogenic variants in candidate disease genes for tooth agenesis in 10 multiplex Turkish families. Novel homozygous and heterozygous variants in LRP6, DKK1, LAMA3, and COL17A1 genes, as well as known variants in WNT10A, were identified as likely pathogenic in isolated tooth agenesis. Novel variants in KREMEN1 were identified as likely pathogenic in 2 families with suspected syndromic tooth agenesis. Variants in more than 1 gene were identified segregating with tooth agenesis in 2 families, suggesting oligogenic inheritance. Structural modeling of missense variants suggests deleterious effects to the encoded proteins. Functional analysis of an indel variant (c.3607+3_6del) in LRP6 suggested that the predicted resulting mRNA is subject to nonsense-mediated decay. Our results support a major role for WNT pathways genes in the etiology of tooth agenesis while revealing new candidate genes. Moreover, oligogenic cosegregation was suggestive for complex inheritance and potentially complex gene product interactions during development, contributing to improved understanding of the genetic etiology of familial tooth agenesis.
Keywords: Anodontia; Female; Genetic Linkage; Genetic Variation; Humans; Intercellular Signaling Peptides and Proteins; Laminin; Low Density Lipoprotein Receptor-Related Protein-6; Male; Membrane Proteins; Mutation, Missense; Pedigree; Real-Time Polymerase Chain Reaction; Turkey; Whole Exome Sequencing; Wnt Proteins

Copy Number Changes Identified Using Whole Exome Sequencing in Nonsyndromic Cleft Lip and Palate in a Honduran Population. - Cai, Yi; Patterson, Karynne E; Reinier, Frederic; Keesecker, Sarah E; Blue, Elizabeth; Bamshad, Michael; Haddad, Joseph (Birth Defects Res, 2017)
BACKGROUND: The majority of cleft lip with or without cleft palate cases appear as an isolated, nonsyndromic entity (NSCLP). With the advent of next generation sequencing, whole exome sequencing (WES) has been used to identify single nucleotide variants and insertion/deletions which cause or increase the risk of NSCLP. However, to our knowledge, there are no published studies using WES in NSCLP to investigate copy number changes (CNCs), which are a major component of human genetic variation. Our study aimed to identify CNCs associated with NSCLP in a Honduran population using WES. METHODS: WES was performed on two to four members of 27 multiplex Honduran families. CNCs were identified using two algorithms, CoNIFER and XHMM. Priority was given to CNCs that were identified in more than one patient and had variant frequencies of less than 5% in reference data sets. RESULTS: WES completion was defined as >90% of the WES target at >8 × coverage and >80% of the WES target at >20 × coverage. Twenty-four CNCs that met our inclusion criteria were identified by both CoNIFER and XHMM. These CNCs were confirmed using quantitative PCR. Pedigree analysis produced three CNCs corresponding to ADH7, AHR, and CRYZ segregating with NSCLP. Two of the three CNCs implicate genes, AHR and ADH7, whose known biological functions could plausibly play a role in NSCLP. CONCLUSION: WES can be used to detect candidate CNCs that may be involved in the pathophysiology of NSCLP. Birth Defects Research 109:1257-1267, 2017. © 2017 Wiley Periodicals, Inc.
Keywords: Adolescent; Adult; Alcohol Dehydrogenase; Alleles; Basic Helix-Loop-Helix Transcription Factors; Child; Child, Preschool; Cleft Lip; Cleft Palate; DNA Copy Number Variations; Family; Female; Gene Frequency; Genetic Variation; High-Throughput Nucleotide Sequencing; Honduras; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Receptors, Aryl Hydrocarbon; Whole Exome Sequencing

De novo mutations in inhibitors of Wnt, BMP, and Ras/ERK signaling pathways in non-syndromic midline craniosynostosis. - Timberlake, Andrew T; Furey, Charuta G; Choi, Jungmin; Nelson-Williams, Carol; Loring, Erin; Galm, Amy; Kahle, Kristopher T; Steinbacher, Derek M; Larysz, Dawid; Persing, John A; Lifton, Richard P (Proc Natl Acad Sci U S A, 2017)
Non-syndromic craniosynostosis (NSC) is a frequent congenital malformation in which one or more cranial sutures fuse prematurely. Mutations causing rare syndromic craniosynostoses in humans and engineered mouse models commonly increase signaling of the Wnt, bone morphogenetic protein (BMP), or Ras/ERK pathways, converging on shared nuclear targets that promote bone formation. In contrast, the genetics of NSC is largely unexplored. More than 95% of NSC is sporadic, suggesting a role for de novo mutations. Exome sequencing of 291 parent-offspring trios with midline NSC revealed 15 probands with heterozygous damaging de novo mutations in 12 negative regulators of Wnt, BMP, and Ras/ERK signaling (10.9-fold enrichment, = 2.4 × 10). had 4 de novo and 14 transmitted mutations; no other gene had more than 1. Four familial NSC kindreds had mutations in genes previously implicated in syndromic disease. Collectively, these mutations contribute to 10% of probands. Mutations are predominantly loss-of-function, implicating haploinsufficiency as a frequent mechanism. A common risk variant near increased the penetrance of mutations and was overtransmitted to patients with de novo mutations in other genes in these pathways, supporting a frequent two-locus pathogenesis. These findings implicate new genes in NSC and demonstrate related pathophysiology of common non-syndromic and rare syndromic craniosynostoses. These findings have implications for diagnosis, risk of recurrence, and risk of adverse neurodevelopmental outcomes. Finally, the use of pathways identified in rare syndromic disease to find genes accounting for non-syndromic cases may prove broadly relevant to understanding other congenital disorders featuring high locus heterogeneity.
Keywords: Adult; Animals; Bone Morphogenetic Proteins; Child; Child, Preschool; Cranial Sutures; Craniosynostoses; Exome; Female; Humans; Male; MAP Kinase Signaling System; Mutation; Osteogenesis; Penetrance; Phenotype; ras Proteins; Sequence Analysis, DNA; Signal Transduction; Smad6 Protein; Whole Exome Sequencing

Diagnosis of Chronic Intestinal Pseudo-obstruction and Megacystis by Sequencing the ACTG2 Gene. - Milunsky, Aubrey; Baldwin, Clinton; Zhang, Xiaoying; Primack, Daniel; Curnow, Adrian; Milunsky, Jeff (J Pediatr Gastroenterol Nutr, 2017)
OBJECTIVES: The diagnosis of chronic intestinal pseudo-obstruction has depended on clinical features, manometry, and imaging. This report aimed to determine the efficacy of sequencing the actin γ-2 (ACTG2) gene for diagnosis. In addition, the goal was to determine how often a mutation would be found in our randomly collected cohort of probands and those probands published previously. METHODS: Whole exome sequencing was performed in 4 probands with chronic intestinal pseudo-obstruction. Subsequently, only the ACTG2 gene was sequenced in another 24 probands (total 28). We analyzed published data of 83 probands and our 28 (total 111) and determined how many had pathogenic variants and the precise genotype. RESULTS: Whole exome and Sanger sequencing revealed a pathogenic variant in the ACTG2 gene in 4 out of 28 of our probands and in 45 out of 83 published probands (49/111 [44.1%]). Moreover, a mutational hotspot in the ACTG2 gene was recognized. Genetic heterogeneity is evident. CONCLUSIONS: Pooled gene sequencing results from 1 individual in each of 111 families enabled a precise diagnosis of an ACTG2 mutation in 49 (44%). The benefit to patients and families of early confirmation of a motility disorder not only helps avoid unnecessary intervention, but also enables institution of appropriate treatments and avoidance of secondary disorders such as malnutrition and poor growth. Knowledge of a pathogenic variant in a parent, with a 50% risk of recurrence, provides an opportunity for genetic counseling.
Keywords: Actins; Adult; Child; Child, Preschool; Chronic Disease; Duodenum; Female; Fetal Diseases; Genetic Markers; Genetic Testing; Humans; Infant; Infant, Newborn; Intestinal Pseudo-Obstruction; Male; Mutation; Sequence Analysis, DNA; Urinary Bladder; Whole Exome Sequencing

Encephalopathy caused by novel mutations in the CMP-sialic acid transporter, SLC35A1. - Ng, Bobby G; Asteggiano, Carla G; Kircher, Martin; Buckingham, Kati J; Raymond, Kimiyo; Nickerson, Deborah A; Shendure, Jay; Bamshad, Michael J; Ensslen, Matthias; Freeze, Hudson H (Am J Med Genet A, 2017)
Transport of activated nucleotide-sugars into the Golgi is critical for proper glycosylation and mutations in these transporters cause a group of rare genetic disorders termed congenital disorders of glycosylation. We performed exome sequencing on an individual with a profound neurological presentation and identified rare compound heterozygous mutations, p.Thr156Arg and p.Glu196Lys, in the CMP-sialic acid transporter, SLC35A1. Patient primary fibroblasts and serum showed a considerable decrease in the amount of N- and O-glycans terminating in sialic acid. Direct measurement of CMP-sialic acid transport into the Golgi showed a substantial decrease in overall rate of transport. Here we report the identification of the third patient with CMP-sialic acid transporter deficiency, who presented with severe neurological phenotype, but without hematological abnormalities.
Keywords: Animals; Brain Diseases; Child; CHO Cells; Cricetinae; Cricetulus; Female; Flow Cytometry; Golgi Apparatus; Humans; Mutation; N-Acetylneuraminic Acid; Nucleotide Transport Proteins; Whole Exome Sequencing

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Rett Syndrome; Whole Exome Sequencing

Exome sequencing in Jewish and Arab patients with rhabdomyolysis reveals single-gene etiology in 43% of cases. - Vivante, Asaf; Ityel, Hadas; Pode-Shakked, Ben; Chen, Jing; Shril, Shirlee; van der Ven, Amelie T; Mann, Nina; Schmidt, Johanna Magdalena; Segel, Reeval; Aran, Adi; Zeharia, Avraham; Staretz-Chacham, Orna; et al. (Pediatr Nephrol, 2017)
BACKGROUND: Rhabdomyolysis is a clinical emergency that may cause acute kidney injury (AKI). It can be acquired or due to monogenic mutations. Around 60 different rare monogenic forms of rhabdomyolysis have been reported to date. In the clinical setting, identifying the underlying molecular diagnosis is challenging due to nonspecific presentation, the high number of causative genes, and current lack of data on the prevalence of monogenic forms. METHODS: We employed whole exome sequencing (WES) to reveal the percentage of rhabdomyolysis cases explained by single-gene (monogenic) mutations in one of 58 candidate genes. We investigated a cohort of 21 unrelated families with rhabdomyolysis, in whom no underlying etiology had been previously established. RESULTS: Using WES, we identified causative mutations in candidate genes in nine of the 21 families (43%). We detected disease-causing mutations in eight of 58 candidate genes, grouped into the following categories: (1) disorders of fatty acid metabolism (CPT2), (2) disorders of glycogen metabolism (PFKM and PGAM2), (3) disorders of abnormal skeletal muscle relaxation and contraction (CACNA1S, MYH3, RYR1 and SCN4A), and (4) disorders of purine metabolism (AHCY). CONCLUSIONS: Our findings demonstrate a very high detection rate for monogenic etiologies using WES and reveal broad genetic heterogeneity for rhabdomyolysis. These results highlight the importance of molecular genetic diagnostics for establishing an etiologic diagnosis. Because these patients are at risk for recurrent episodes of rhabdomyolysis and subsequent risk for AKI, WES allows adequate prophylaxis and treatment for these patients and their family members and enables a personalized medicine approach.
Keywords: Adolescent; Adult; Arabs; Child; Exome; Genetic Predisposition to Disease; Humans; Jews; Mutation; Rhabdomyolysis; Whole Exome Sequencing

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin; Whole Exome Sequencing

Identification of GAA variants through whole exome sequencing targeted to a cohort of 606 patients with unexplained limb-girdle muscle weakness. - Johnson, Katherine; Topf, Ana; Bertoli, Marta; Phillips, Lauren; Claeys, Kristl G; Stojanovic, Vidosava Rakocevic; Perić, Stojan; Hahn, Andreas; Maddison, Paul; Akay, Ela; Bastian, Alexandra E; Łusakowska, Anna; et al. (Orphanet J Rare Dis, 2017)
BACKGROUND: Late-onset Pompe disease is a rare genetic neuromuscular disorder caused by a primary deficiency of α-glucosidase and the associated accumulation of glycogen in lysosomal vacuoles. The deficiency of α-glucosidase can often be detected using an inexpensive and readily accessible dried blood spot test when Pompe disease is suspected. Like several neuromuscular disorders, Pompe disease typically presents with progressive weakness of limb-girdle muscles and respiratory insufficiency. Due to the phenotypic heterogeneity of these disorders, however, it is often difficult for clinicians to reach a diagnosis for patients with Pompe disease. Six hundred and six patients from a European population were recruited onto our study. Inclusion criteria stipulated that index cases must present with limb-girdle weakness or elevated serum creatine kinase activity. Whole exome sequencing with at least 250 ng DNA was completed using an Illumina exome capture and a 38 Mb baited target. A panel of 169 candidate genes for limb-girdle weakness was analysed for disease-causing variants. RESULTS: A total of 35 variants within GAA were detected. Ten distinct variants in eight unrelated index cases (and four siblings not sequenced in our study) were considered disease-causing, with the patients presenting with heterogeneous phenotypes. The eight unrelated individuals were compound heterozygotes for two variants. Six patients carried the intronic splice site c.-13 T > G transversion and two of the six patients also carried the exonic p.Glu176ArgfsTer45 frameshift. Four of the ten variants were novel in their association with Pompe disease. CONCLUSIONS: Here, we highlight the advantage of using whole exome sequencing as a tool for detecting, diagnosing and treating patients with rare, clinically variable genetic disorders.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; alpha-Glucosidases; Child; Child, Preschool; Cohort Studies; Female; Genetic Variation; Glycogen Storage Disease Type II; Humans; Male; Middle Aged; Muscle Weakness; Muscular Dystrophies, Limb-Girdle; Whole Exome Sequencing; Young Adult

Mutations in DYNC2H1, the cytoplasmic dynein 2, heavy chain 1 motor protein gene, cause short-rib polydactyly type I, Saldino-Noonan type. - Badiner, N; Taylor, S P; Forlenza, K; Lachman, R S; Bamshad, M; Nickerson, D; Cohn, D H; Krakow, D (Clin Genet, 2017)
The short-rib polydactyly syndromes (SRPS) are autosomal recessively inherited, genetically heterogeneous skeletal ciliopathies. SRPS phenotypes were historically categorized as types I-IV, with type I first delineated by Saldino and Noonan in 1972. Characteristic findings among all forms of SRP include short horizontal ribs, short limbs and polydactyly. The SRP type I phenotype is characterized by a very small thorax, extreme micromelia, very short, poorly mineralized long bones, and multiple organ system anomalies. To date, the molecular basis of this most severe type of SRP, also known as Saldino-Noonan syndrome, has not been determined. We identified three SRP cases that fit the original phenotypic description of SRP type I. In all three cases, exome sequence analysis revealed compound heterozygosity for mutations in DYNC2H1, which encodes the main component of the retrograde IFT A motor, cytoplasmic dynein 2 heavy chain 1. Thus SRP type I, II, III and asphyxiating thoracic dystrophy (ATD), which also result from DYNC2H1 mutations. Herein we describe the phenotypic features, radiographic findings, and molecular basis of SRP type I.
Keywords: Cytoplasmic Dyneins; Ellis-Van Creveld Syndrome; Female; Fetus; Genetic Heterogeneity; Genetic Predisposition to Disease; Humans; Infant, Newborn; Mutation; Phenotype; Pregnancy; Radiography; Short Rib-Polydactyly Syndrome; Whole Exome Sequencing

A postnatal role for embryonic myosin revealed by MYH3 mutations that alter TGFβ signaling and cause autosomal dominant spondylocarpotarsal synostosis. - Zieba, Jennifer; Zhang, Wenjuan; Chong, Jessica X; Forlenza, Kimberly N; Martin, Jorge H; Heard, Kelly; Grange, Dorothy K; Butler, Merlin G; Kleefstra, Tjitske; Lachman, Ralph S; Nickerson, Deborah; Regnier, Michael; et al. (Sci Rep, 2017)
Spondylocarpotarsal synostosis (SCT) is a skeletal disorder characterized by progressive vertebral, carpal and tarsal fusions, and mild short stature. The majority of affected individuals have an autosomal recessive form of SCT and are homozygous or compound heterozygous for nonsense mutations in the gene that encodes the cytoskeletal protein filamin B (FLNB), but a subset do not have FLNB mutations. Exome sequence analysis of three SCT patients negative for FLNB mutations identified an autosomal dominant form of the disease due to heterozygosity for missense or nonsense mutations in MYH3, which encodes embryonic myosin. Cells transfected with the MYH3 missense mutations had reduced TGFβ signaling, revealing a regulatory role for embryonic myosin in the TGFβ signaling pathway. In wild-type mice, there was persistent postnatal expression of embryonic myosin in the small muscles joining the neural arches of the spine suggesting that loss of myosin function in these muscles contribute to the disease. Our findings demonstrate that dominant mutations in MYH3 underlie autosomal dominant SCT, identify a postnatal role for embryonic myosin and suggest that altered regulation of signal transduction in the muscles within the spine may lead to the development of vertebral fusions.
Keywords: Abnormalities, Multiple; Alleles; Bone Morphogenetic Proteins; Cytoskeletal Proteins; Female; Genes, Dominant; Genotype; Humans; Lumbar Vertebrae; Male; Musculoskeletal Diseases; Mutation; Myosins; Phenotype; Radiography; Scoliosis; Signal Transduction; Synostosis; Thoracic Vertebrae; Transforming Growth Factor beta; Whole Exome Sequencing

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
Importance: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. Objective: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. Design, Setting, and Participants: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. Main Outcomes and Measures: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. Results: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. Conclusions and Relevance: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas; Whole Exome Sequencing

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Muzny, Donna; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male; Whole Exome Sequencing

Keratoacanthoma Shares Driver Mutations with Cutaneous Squamous Cell Carcinoma. - Lim, Young H; Fisher, Jonathan M; Bosenberg, Marcus W; Choate, Keith A; Ko, Christine J (J Invest Dermatol, 2016)
Keywords: Aged; Aged, 80 and over; Biomarkers, Tumor; Biopsy; Carcinoma, Squamous Cell; Cohort Studies; Diagnosis, Differential; Exome; Female; Humans; Keratoacanthoma; Loss of Heterozygosity; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Skin; Skin Neoplasms; Whole Exome Sequencing